Composite insulating coating, preparation method of composite insulating coating, battery cell and application of battery cell

By setting up a composite insulating coating on the inner wall surface of the battery cell shell, dynamic crosslinking network structure and chemical bonding are used to improve binding force and stability, the problems of poor binding force and insufficient spontaneous blocking corrosion ability of the existing bond layer are solved, and higher cell safety and service life are achieved.

CN119651011APending Publication Date: 2025-03-18HUAWEI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311205120.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The bonding layer provided on the inner wall of the existing battery cell shell has problems such as poor bonding force between coatings, poor interfacial bonding stability, and lack of spontaneous corrosion blocking ability.

Method used

A composite insulating coating is adopted, including a layered film layer and an adhesive layer arranged in a stack. The film layer contains organic components with negatively charged functional groups and positively charged metal ions, and a dynamic crosslinked network structure is formed through complexation. The organic matter containing polar functional groups in the adhesive layer can form chemical bonds with negatively charged functional groups in the film layer.

Benefits of technology

The bonding force and stability of the composite insulating coating are improved, the effect of spontaneous corrosion blocking is achieved, the covering characteristics and toughness of the electrolyte are enhanced, the corrosion of the electrolyte on the substrate is reduced, and the safety and service life of the battery cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651011A_ABST
    Figure CN119651011A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite insulating coating, a preparation method thereof, a battery cell and application of the battery cell. The composite insulating coating comprises a coating layer and a bonding layer which are arranged in a laminated mode, the coating layer is arranged on the surface of the application matrix in an attached mode and comprises organic components with electronegative functional groups and electropositive metal ions, and a dynamic cross-linked network structure is formed through complexation; the bonding layer is arranged on the surface of the coating layer and comprises an organic matter containing a polar functional group; at least on the interface of the coating layer and the bonding layer, the polar functional group in the organic matter and the electronegative functional group in the organic component form chemical bonding. The composite insulating coating can collaboratively seal electrolyte, has high mechanical stability, and can block long-period corrosion; meanwhile, the material has high insulativity, high toughness and an interface self-repairing function, can improve the hidden danger of microcracks caused by uneven stress of a matrix when being applied to a battery cell, reduces the risk of abnormal high-voltage electric breakdown of the matrix, and improves the long-term use reliability of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and in particular relates to a composite insulating coating and a preparation method thereof, a battery cell and applications thereof. Background Art

[0002] Accelerate the rapid development and application of power and energy storage cells. On the one hand, under the background of fast charging and long cycle, the high-voltage platform of power cells has evolved from 400V to 800V, and the 800V high-voltage platform has gradually begun to land; on the other hand, large-scale commercial storage also shows an iterative evolution trend of "capacity upward", gradually developing from 2MWh to 5MWh, so the system has a higher voltage. Based on this dual evolution direction, the safety of the battery cell is particularly important, and higher requirements are placed on the voltage resistance of the battery cell.

[0003] Common safety failure problems in the application of battery cells include internal corrosion and external insulation failure. Abnormal internal short circuits during the application of battery cells often cause corrosion of the shell, and eventually leakage failure occurs. The internal explosion-proof valve of the battery cell is relatively weak, and it is easy to cause failure and leakage after long-term corrosion by the electrolyte. In addition, the battery cell is easily exposed to corrosive substances such as acid or alkali during storage or use, which corrodes the aluminum shell from the outside and causes leakage, thereby causing the negative electrode and the shell to be short-circuited externally, causing the shell to be embedded with lithium and electrochemical corrosion leakage. The external short circuit of different battery cell shells at the system end will generate a high voltage in series, and the abnormal local arcing and deflagration of the electrolyte under high voltage will also cause the aluminum shell to break and leak. How to block the long-term corrosion of the battery cell, improve the uneven stress corrosion of the explosion-proof valve, and reduce the risk of abnormal high voltage breakdown of the shell are key factors to ensure the safety of the battery cell. At present, setting an adhesive layer on the inner wall of the battery cell shell is the main method to solve the above problems. However, the existing adhesive layer set on the inner wall of the battery cell shell has problems such as poor bonding between the coatings, poor interface bonding stability, and lack of spontaneous corrosion blocking ability.

[0004] Therefore, it is particularly important to develop a composite insulating coating suitable for protecting battery cells and / or explosion-proof valves to block long-term corrosion of battery cells, improve uneven stress corrosion of explosion-proof valves, and reduce the risk of abnormally high voltage breakdown of battery cell shells, thereby ensuring the safety of battery cells. Summary of the invention

[0005] The purpose of the present application is to provide a composite insulating coating and a preparation method thereof, as well as a battery cell and its application, aiming to solve the problems of poor bonding strength between the coatings of the composite adhesive layer arranged on the inner wall surface of the existing battery cell shell and / or the inner surface of the explosion-proof valve, poor interface bonding stability, and lack of spontaneous corrosion blocking ability.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] The first aspect of the present application provides a composite insulating coating, comprising a laminated film layer and an adhesive layer, wherein the film layer is adhered to the surface of an application substrate, the film layer comprises an organic component with negatively charged functional groups and positively charged metal ions, and the positively charged metal ions form a dynamically cross-linked network structure with the negatively charged functional groups; the adhesive layer is arranged on the surface of the film layer, has electrolyte barrier properties, the adhesive layer comprises an organic substance containing polar functional groups, and the polar functional groups in the adhesive layer form chemical bonds with the negatively charged functional groups in the film layer at the interface.

[0008] The composite insulating coating provided in the present application has a double-layer structure of a film layer and an adhesive layer arranged in layers, wherein the film layer includes an organic component with negatively charged functional groups and positively charged metal ions, and the negatively charged functional groups in the organic component can form a dynamic cross-linked network structure at the microscopic level through complexation with the positively charged metal ions, on the one hand, so that the composite insulating coating has high covering properties and toughness to the electrolyte, and effectively reduces the corrosion of the electrolyte to the application substrate; on the other hand, the complexed positively charged metal ions in the dynamic cross-linked network structure can act as an inhibitor. When the substrate has defects such as damage and gaps due to corrosion, the positively charged metal ions in the film layer can be converted into insoluble metal precipitates by a physicochemical reaction with an acidic or alkaline medium. The insoluble metal precipitates are continuously precipitated and aggregated at the defects, which can effectively fill the defects of the composite insulating coating and the substrate, thereby achieving spontaneous corrosion blocking and better protecting the substrate from corrosion. In addition, the film layer including the organic components with negatively charged functional groups and the positively charged metal ions has a good surface bonding effect with the application substrate, and can be stably and firmly bonded to the surface of the metal substrate to protect the substrate. The bonding layer includes organic matter containing polar functional groups, which does not react with the electrolyte and has high electrolyte hiding power, that is, electrolyte barrier properties, further reducing the corrosion of the electrolyte to the application substrate. In addition, the polar functional groups of the organic matter in the bonding layer can form chemical bonds with the negatively charged functional groups in the film layer at the interface, which not only improves the bonding force and bonding stability between the film layer and the bonding layer, and ensures the stability of the coating interface; but also improves the self-repairing function of the composite insulating coating, which can better ensure the stable conformality of the double-layer structure interface, thereby improving the protective effect of the composite insulating coating on the application substrate. In addition, the bonding layer has high toughness, which can provide stress buffering for the deformation of the application substrate, reduce the risk of deformation of the application substrate, and further improve the application stability of the substrate.

[0009] As some possible implementations of the composite insulating coating of the present application, the mass percentage of the positively charged metal ions in the film layer is 1% to 30%, preferably 10% to 20%. In this case, the mass percentage of the positively charged metal ions in the film layer ensures that the negatively charged functional groups in the organic component can fully complex with the positively charged metal ions to form a dynamic cross-linked network structure, ensuring the covering property of the electrolyte, the defect filling effect of the composite insulating coating, and the spontaneous corrosion blocking effect on the application substrate.

[0010] As some possible implementations of the composite insulating coating of the present application, in the film layer, the positively charged metal ions include at least one of Cr ions, Zr ions, Ni ions, Co ions, Mo ions, Zn ions, Mn ions, V ions, and Ce ions. In this case, these positively charged metal ions in the inorganic component can fully complex with the negatively charged functional groups in the organic component to form a dynamic cross-linked network structure, forming a film layer that has a covering property for the electrolyte and is tough.

[0011] As some possible implementations of the composite insulating coating of the present application, the organic components with negatively charged functional groups include at least one of polyester, polyether, polyol, polyolefin acid, polyaldehyde, polyketone, polyamide, and polysiloxane. These organic components with negatively charged functional groups do not react with the electrolyte, so that the film layer has electrolyte covering properties and toughness, which can protect the application substrate from corrosion and relieve the stress caused by substrate deformation, and all contain negatively charged functional groups, which can be complexed with positively charged metal ions to form a dynamic cross-linked network structure.

[0012] As some possible implementations of the composite insulating coating of the present application, the negatively charged functional group in the organic component includes an oxygen-containing functional group A. As some possible implementations of the composite insulating coating of the present application, the oxygen-containing functional group A includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an ester group, an aldehyde group, a ketone group, an ether group, and an amide group. In this case, the oxygen-containing functional group A in the organic component can form a complex with the positively charged metal ion, that is, a stable chemical bond is formed through a coordination bond, thereby forming a dynamically cross-linked network structure.

[0013] As some possible implementations of the composite insulating coating of the present application, the expression of the dynamically cross-linked network structure includes -M1-O-M2-O-…-Mi-, wherein M1, M2, Mi are independently selected from at least one of Cr, Zr, Ni, Co, Mo, Zn, Mn, V, and Ce, and i is a positive integer greater than 2. Among them, M1, M2, and Mi can be selected from the same or different metal elements.

[0014] As some possible implementations of the composite insulating coating of the present application, the polar functional groups in the organic matter include at least one of nitrogen-containing functional groups, oxygen-containing functional groups B, and fluorine-containing functional groups. In this case, the polar functional groups such as nitrogen-containing functional groups, oxygen-containing functional groups B, and fluorine-containing functional groups in the organic matter can all be chemically bonded to the negatively charged functional groups of the organic components in the film layer through hydrogen bonds or other forms.

[0015] As some possible implementations of the composite insulating coating of the present application, the nitrogen-containing functional group includes at least one of an amide group, an amine group, and an imine group;

[0016] As some possible implementations of the composite insulating coating of the present application, the oxygen-containing functional group B includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an ester group, an aldehyde group, a ketone group, an ether group, and an amide group;

[0017] As some possible implementations of the composite insulating coating of the present application, the fluorine-containing functional group includes at least one of a fluorocarbon group and a fluorooxy group.

[0018] As some possible implementation methods of the composite insulating coating of the present application, the polar functional groups in the organic matter and the negatively charged functional groups in the organic component form hydrogen bonds at the interface between the film layer and the adhesive layer. In this case, the interfacial chemical bonding can significantly improve the bonding force and bonding stability between the film layer and the adhesive layer, improve the self-repairing function of the composite insulating coating, better ensure the stable conformality of the double-layer structure interface, and thus improve the protective effect of the composite insulating coating on the application substrate.

[0019] As some possible implementation methods of the composite insulating coating of the present application, the organic matter includes at least one of modified polyolefin, polyvinylidene fluoride, polyamide, polyimide, polyacrylonitrile, modified polyaramid, polyetheretherketone, polyethylene terephthalate, polyphenylene sulfide, and polybenzimidazole. These organic substances used all contain polar functional groups such as nitrogen-containing functional groups, oxygen-containing functional groups, and fluorine-containing functional groups, and can form chemical bonds such as covalent bonds and hydrogen bonds with the negatively charged functional groups of the organic components in the film layer, thereby improving the bonding force and bonding stability between the film layer and the adhesive layer, improving the self-repairing function of the composite insulating coating, and better ensuring the stable conformality of the double-layer structure interface, thereby improving the protective effect of the composite insulating coating on the application substrate.

[0020] As some possible implementations of the composite insulating coating of the present application, the molar molecular weight of the organic matter is 3000 g / mol to 300000 g / mol. The molecular weight has a wide range, and the molar molecular weight of the organic matter within this range can effectively ensure the formed bonding layer has the characteristics of covering effect on the electrolyte, insulation performance, high toughness, etc.

[0021] As some possible implementations of the composite insulating coating of the present application, the thickness of the composite insulating coating is 10μm to 1000μm, preferably 40μm to 500μm; under this thickness condition, the composite insulating coating can ensure the protective effect of the composite insulating coating on the battery component application substrate such as the battery cell shell and explosion-proof valve, avoid the electrolyte from contacting and corroding the substrate, effectively block the long-term corrosion of the explosion-proof valve and / or the battery cell shell, block charge conduction, and prevent the application substrate from being electrically broken down under conditions such as abnormally high voltage.

[0022] As some possible implementations of the composite insulating coating of the present application, the thickness of the film layer is 5 μm to 500 μm, preferably 20 μm to 250 μm; under this thickness condition, it ensures high hiding properties and toughness for the electrolyte, reduces corrosion of the electrolyte to the application substrate, ensures the effect of filling defects of the composite insulating coating, ensures the effect of self-repair of the composite insulating coating, and ensures the effect of spontaneously blocking corrosion of the application substrate.

[0023] As some possible implementations of the composite insulating coating of the present application, the thickness of the bonding layer is 5 μm to 500 μm, preferably 20 μm to 250 μm. Under this thickness condition, the high covering property of the electrolyte is ensured, and the corrosion of the electrolyte to the application substrate is reduced. It is ensured that the polar functional groups of the organic matter in the bonding layer can form a dynamic cross-linked chemical bond with the negatively charged functional groups in the film layer at least at the interface between the film layer and the bonding layer, ensuring the bonding strength and bonding stability between the film layer and the bonding layer.

[0024] As some possible implementations of the composite insulating coating of the present application, the surface density of the composite insulating coating is 0.5 mg / m 2 ~50 mg / m 2 , preferably 1 mg / m 2 ~20 mg / m 2 This surface density condition ensures the composite insulating coating's covering property for the electrolyte and the stress buffering effect for the deformation of the application substrate, while ensuring the composite insulating coating's defect filling effect and self-repairing effect, as well as the spontaneous corrosion blocking effect for the application substrate.

[0025] As some possible implementations of the composite insulating coating of the present application, the dielectric strength of the composite insulating coating is not less than 5000V / mm, preferably not less than 10000V / mm. In this case, having a high dielectric strength indicates that the composite insulating coating has good insulation performance, can withstand high voltage without dielectric breakdown, and can effectively prevent the composite insulating coating from being electrically broken down.

[0026] As some possible implementations of the composite insulating coating of the present application, the softening temperature of the composite insulating coating is 70°C to 250°C, preferably 90°C to 200°C. Under this softening temperature condition, the composite insulating coating has a higher softening temperature, ensuring that the composite insulating coating protects the substrate to operate safely during normal operation. When under extreme conditions, the composite insulating coating may soften and fail in advance, such as participating in the preset pressure adjustment of the explosion-proof valve through softening, reducing the valve opening pressure and timely releasing the internal pressure and heat of the battery cell, which greatly ensures the airtightness and safety function of the explosion-proof valve.

[0027] Accordingly, in a second aspect, the present application provides a method for preparing a composite insulating coating, comprising the following steps:

[0028] After preparing a mixed slurry including an organic component with negatively charged functional groups and a metal component with positively charged metal ions, the mixed slurry is made into a film layer on the surface of an application substrate to form a membrane layer; in the membrane layer, the positively charged metal ions and the negatively charged functional groups form a dynamically cross-linked network structure;

[0029] Organic matter containing polar functional groups is made into a film layer on the surface of the film layer to form an adhesive layer with electrolyte barrier properties, thereby obtaining a composite insulating coating; at the interface between the film layer and the adhesive layer, the polar functional groups in the organic matter form chemical bonds with the negatively charged functional groups in the film layer.

[0030] The preparation method of the composite insulating coating of the present application comprises preparing a mixed slurry including an organic component with negatively charged functional groups and a metal component with positively charged metal ions, and then forming a film layer on the surface of the application substrate, so that the negatively charged functional groups in the organic component and the positively charged metal ions in the inorganic component form a dynamic cross-linked network structure at the microscopic level through complexation. Organic matter containing polar functional groups is formed into a film layer on the surface of the film layer, so that the polar functional groups in the organic matter and the negatively charged functional groups in the organic components of the film layer form chemical bonds, thereby forming a stable bonding layer on the surface of the film layer to obtain a composite insulating coating. The preparation process is simple and suitable for large-scale industrial production and application. The film layer in the prepared composite insulating coating has high covering properties and toughness for the electrolyte, can cooperate to seal the electrolyte, has high mechanical stability, and effectively reduces the corrosion of the electrolyte to the application substrate; and the positively charged metal ions can be converted into insoluble metal precipitates through physical and chemical reactions with acidic or alkaline media, which are continuously precipitated and aggregated, effectively filling the defects of the composite insulating coating and the substrate, achieving a self-repairing effect on the composite insulating coating, and spontaneously blocking corrosion of the application substrate, better protecting the substrate from corrosion. In addition, the bonding layer is arranged on the surface of the film layer, and the organic matter containing polar functional groups can form chemical bonds with the negatively charged functional groups in the organic components of the film layer at the interface, thereby improving the bonding force and bonding stability between the film layer and the bonding layer, ensuring the stability of the coating interface, improving the self-repairing function of the composite insulating coating, better ensuring the stable conformality of the double-layer structure interface, and improving the protective effect of the composite insulating coating on the application substrate. In addition, the composite insulating coating has high toughness and high insulation, which can reduce the risk of deformation of the application substrate and the risk of abnormal high-voltage electrical breakdown, and improve the application stability of the substrate.

[0031] As some possible implementations of the method for preparing the composite insulating coating of the present application, the preparation of the film layer includes the following steps:

[0032] Dissolving an organic component having a negatively charged functional group in a first solvent to obtain a first solution;

[0033] dissolving a metal component having positively charged metal ions in a second solvent to obtain a second solution;

[0034] The first solution and the second solution are mixed, washed, and extracted to obtain a polymer complexed with metal ions;

[0035] After the metal ion complexing polymer is dissolved in an organic solvent, a film layer is formed on the surface of the application substrate to obtain a film layer.

[0036] As some possible implementations of the preparation method of the composite insulating coating of the present application, the metal component includes an organic metal salt and / or an inorganic metal salt. In this case, the positively charged metal ions in the organic metal salt and / or the inorganic metal salt are easily dissociated and fully complexed with the negatively charged functional groups in the organic component to form a dynamic cross-linked network structure, ensuring the covering property of the film layer on the electrolyte and the defect filling effect of the film layer, so that the composite insulating coating has a self-repairing effect and produces a spontaneous corrosion blocking effect on the application substrate.

[0037] As some possible implementations of the preparation method of the composite insulating coating of the present application, the organic component includes at least one of polyester, polyether, polyol, polyolefin acid, polyaldehyde, polyketone, polyamide, and polysiloxane. These organic components with negatively charged functional groups do not react with the electrolyte, so that the film layer has electrolyte covering properties and toughness, which can protect the application substrate from corrosion and relieve the stress caused by substrate deformation, and all contain negatively charged functional groups, which can be complexed with positively charged metal ions to form a dynamic cross-linked network structure.

[0038] As some possible implementations of the method for preparing the composite insulating coating of the present application, the first solvent and / or the second solvent are independently selected from at least one of a polar solvent, a dipolar solvent, and a non-polar solvent. These solvents have good solubility for both organic components with negatively charged functional groups and metal components with positively charged metal ions.

[0039] As some possible implementations of the method for preparing the composite insulating coating of the present application, the preparation of the bonding layer includes the steps of:

[0040] The preparation of the bonding layer comprises the following steps: preparing the organic matter containing polar functional groups into a film layer with a preset morphology, and then compounding it onto the surface of the film layer by hot pressing to obtain the bonding layer;

[0041] Alternatively, after the organic matter containing polar functional groups is made into an insulating paste, the insulating paste is deposited on the surface of the film layer and dried to obtain the bonding layer.

[0042] In a third aspect, the present application provides a battery cell, comprising a battery pole core, a battery cell shell and a cover assembly, wherein the cover assembly comprises an explosion-proof valve, and the above-mentioned composite insulating coating, or the composite insulating coating prepared by the above-mentioned method, is provided at least on the inner wall surface of the battery cell shell and / or the inner surface of the explosion-proof valve.

[0043] The inner wall surface of the battery shell and / or the inner side surface of the explosion-proof valve in the battery core of the present application is provided with the above-mentioned composite insulating coating, which includes a double-layer structure of a laminated film layer and an adhesive layer, wherein the film layer is attached to the inner wall surface of the battery shell and / or the inner side surface of the explosion-proof valve, and the adhesive layer faces the battery pole core. The composite insulating coating has high electrolyte covering properties and stability, and can effectively block the long-term corrosion of the explosion-proof valve and / or the battery shell. At the same time, the composite insulating coating has high insulation, high toughness and self-repairing function, which can effectively improve the hidden danger of microcracks caused by uneven stress of the battery shell and / or the explosion-proof valve, reduce the risk of leakage caused by abnormal high-voltage electrical breakdown of the battery shell and / or the explosion-proof valve, and improve long-term reliability. At the same time, it can participate in the preset pressure adjustment of the explosion-proof valve. Under extreme conditions, the composite insulating coating can soften and fail in advance, reduce the valve opening pressure and release the internal pressure and heat of the battery in time, which greatly guarantees the sealing and safety functions of the explosion-proof valve. Therefore, through the application of composite insulating coating, the safety, stability, service life and other performance of the battery cell are significantly improved, giving the battery cell a better and broader application prospect.

[0044] In a fourth aspect, the present application provides a battery module, wherein the battery module comprises a plurality of the above-mentioned battery cells.

[0045] The battery module provided in the present application includes the battery cells with high safety factor, good stability and excellent electrochemical performance, thus improving the safety performance and electrochemical performance of the battery module.

[0046] In a fifth aspect, the present application provides a battery pack, comprising a plurality of the above-mentioned battery modules.

[0047] The battery pack provided in the present application includes the battery module with high safety performance and electrochemical performance, so the battery pack also has excellent safety performance and electrochemical performance.

[0048] In a sixth aspect, the present application provides an electrical device, wherein the electrical device comprises the above-mentioned battery cell, or the above-mentioned battery module, or the above-mentioned battery pack.

[0049] The electrical equipment provided in the present application improves the electrical safety, stability and other performances of the electrical equipment by adopting the above-mentioned battery cells with high safety factor, good stability and excellent electrochemical performance, or the above-mentioned battery modules or battery packs with excellent safety performance and electrochemical performance.

[0050] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 is a schematic diagram of the structure of the composite insulating coating provided in an embodiment of the present application;

[0052] Figure 2 It is a schematic diagram of a process for preparing a composite insulating coating provided in an embodiment of the present application;

[0053] Figure 3 It is a schematic diagram of the explosion structure of the battery cell provided in an embodiment of the present application;

[0054] Figure 4 is a schematic diagram of a composite insulating coating provided on the inner wall surface of a battery cell housing provided in an embodiment of the present application;

[0055] Figure 5 It is a schematic diagram of the explosion structure of the explosion-proof valve provided in the embodiment of the present application;

[0056] Figure 6 It is a schematic diagram of the structure explosion of the battery module provided in the embodiment of the present application;

[0057] Figure 7 This is a Raman spectrum test diagram of the bonding layer in the composite insulating coating provided in Example 1 of the present application;

[0058] Figure 8 This is an infrared spectrum test chart of the bonding layer in the composite insulating coating provided in Example 1 of the present application;

[0059] Fig. 9 This is the XPS full spectrum test chart of the film layer in the composite insulating coating provided in Example 1 of the present application;

[0060] Fig.10 This is the XPS Cr2p spectrum of the film layer in the composite insulating coating provided in Example 1 of the present application;

[0061] Fig.11 This is an electrochemical corrosion test diagram after the composite insulating coating provided in Example 1 of the present application is applied to an explosion-proof valve;

[0062] Fig.12 This is an XPS spectrum test diagram of the composite insulating coating provided in Example 1 of the present application after being applied to an explosion-proof valve for electrochemical corrosion. DETAILED DESCRIPTION

[0063] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0064] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0065] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0066] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0067] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0068] The term "explosion-proof valve" refers to a thin-walled valve body installed on the battery cover assembly. When the internal pressure of the battery exceeds the specified value, the explosion-proof valve body will first rupture and release air, releasing pressure to prevent the battery from bursting. The explosion-proof valve has an ingenious structure, and is often laser welded to secure two metal sheets of a certain shape. When the internal pressure of the battery rises to a certain value, the metal sheet ruptures from the designed groove position to prevent the battery from further expanding and causing an explosion.

[0069] The term "explosion-proof valve notch" indicates that the explosion-proof valve plate is designed with additional reinforcing ribs and bursting notches. When the explosion-proof valve is opened, the explosion-proof valve plate can evenly bear the pressure and crack along the notches, opening outward as a whole to prevent the explosion-proof plate fragments from damaging other electrical components and causing secondary injuries.

[0070] The term "dielectric strength" refers to the measure of the electrical strength of a material as an insulator. It is defined as the maximum voltage per unit thickness that a specimen can withstand when it is punctured, expressed as volts per unit thickness, in units of kilovolts per millimeter or volts per meter. The greater the dielectric strength of a substance, the better the material is as an insulator.

[0071] The term "core" refers to a single unit formed by winding or stacking positive and negative electrode sheets. The core components include positive electrode sheets, negative electrode sheets and separators.

[0072] The term "battery cell" refers to a single electrochemical cell containing positive and negative electrodes. It is the smallest unit of a power battery and also an energy storage unit. The components of a battery cell include positive and negative electrodes, electrolyte, and diaphragm.

[0073] The term "module" means that when multiple battery cells are encapsulated together in the same outer shell frame and connected to the outside through a unified boundary, this forms a module.

[0074] The term "battery pack" refers to the combination of several modules that are controlled or managed together by the battery management system (BMS) and the thermal management system. The unified whole is called a battery pack.

[0075] The term "PTFE" is the abbreviation of Polytetrafluoroethylene, which is a high molecular polymer made by polymerizing tetrafluoroethylene as a monomer. Its chemical formula is (C2F4)n. It has excellent heat and cold resistance and can be used for a long time at -180 to 260°C. This material is resistant to acids, alkalis, and various organic solvents, and is almost insoluble in all solvents. At the same time, polytetrafluoroethylene is resistant to high temperatures and has an extremely low friction coefficient.

[0076] The term "PFA" is an abbreviation of Perfluoroalkoxy, which is a plastic, namely a copolymer of a small amount of perfluoropropyl perfluorovinyl ether and polytetrafluoroethylene. The melt adhesion of PFA is enhanced, the melt viscosity is reduced, and the performance is unchanged compared with polytetrafluoroethylene, so it can be directly processed into products using ordinary thermoplastic molding methods. PFA is suitable for making corrosion-resistant parts, wear-reducing and wear-resistant parts, seals, insulation parts and medical equipment parts, high-temperature wires, cable insulation layers, anti-corrosion equipment, sealing materials, pump valve bushings and chemical containers.

[0077] At present, judging from the development of the market situation, under the background of fast charging and long cycle, the high-voltage platform of power batteries has evolved from 400V to 800V, and the 800V high-voltage platform has gradually begun to land. In addition, large-scale commercial storage also shows an iterative evolution trend of "capacity upward", gradually developing from 2MWh to 5MWh, so the system has a higher voltage. Based on the dual evolutionary directions of high-voltage platform and high capacity of battery cells, the strong electrical safety of battery cells is particularly important, and higher requirements are also placed on the voltage resistance of battery cells.

[0078] Common safety failure issues in battery cell applications include internal corrosion and external insulation failure. Among them, the safety issues caused by internal corrosion mainly include: abnormal internal short circuits during the application of battery cells often cause shell corrosion, and eventually leakage failure; the internal explosion-proof valve of the battery cell is relatively weak, and long-term corrosion by the electrolyte can easily lead to failure due to scratches and leakage. The safety issues caused by external insulation failure mainly include: the battery cell is easily exposed to corrosive substances such as acid or alkali during storage or use, which corrodes the aluminum shell from the outside and causes leakage, thereby causing a short circuit between the negative electrode and the outside of the shell, which will cause the shell to embed lithium and cause electrochemical corrosion and leakage; and the external short circuit of different battery cell shells on the system end will generate a high voltage in series, and the abnormal local arcing and deflagration of the electrolyte under high voltage will also cause holes in the aluminum shell to leak.

[0079] In order to alleviate the safety problems caused by internal corrosion and external insulation failure of the battery cell, the long-term corrosion of the battery cell is blocked, the stress uneven corrosion of the explosion-proof valve is improved, the risk of abnormal high voltage breakdown of the shell is reduced, and the safety of the battery cell is improved. Studies have found that providing an insulating layer on the inner wall surface of the battery cell shell and / or the inner side surface of the explosion-proof valve (i.e., the surface of the explosion-proof valve facing the inside of the battery cell) can effectively alleviate the problems of internal corrosion and external insulation failure of the battery cell. In some known technologies, an insulating layer of a double-layer structure is formed by anisotropically spraying insulating powder coating on the inner wall of the battery cell shell by electrostatic spraying. The insulating layer of the double-layer structure includes an outer coating and an inner coating; the inner coating is an insulating material such as a resin with high thermal conductivity or low thermal conductivity, and the outer coating is often made by coating with PTFE emulsion or PFA emulsion. The bonding ability of the outer coating and the inner coating in this double-layer insulating layer cannot be guaranteed, and it does not have the ability to spontaneously block corrosion. In some other known technologies, the shell of the battery cell includes: a metal substrate, an insulating coating and a heat-absorbing coating; the metal substrate has a cavity portion, the insulating coating is attached to the inner surface of the metal substrate facing the cavity portion; the heat-absorbing coating is attached to the insulating coating. The insulating coating can separate the electrolyte in the battery cell from the metal substrate to prevent the metal substrate from being corroded by the electrolyte. In addition, the heat-absorbing coating is arranged on the insulating coating to absorb the heat released during the charging and discharging process of the battery, thereby stabilizing the performance of the battery. However, the heat-absorbing coating is prone to cause a difference in thermal expansion between the inner and outer coatings, thereby reducing the interface bonding stability. In some other known technologies, a multi-layer insulating layer is arranged on the inner wall surface of the battery cell shell, and the inner layer of the multi-layer insulating layer is a maleic anhydride modified polypropylene layer, the middle layer is a copolymerized polypropylene layer, and the outer layer is a homopolymerized polyacrylic acid layer. The bonding stability between the multi-layer coatings in the insulating layer is poor, and long-term reliability (deformation / corrosion protection) is difficult to guarantee. In other known technologies, an insulating protective layer is provided on the inner wall surface of the battery cell shell and the surface with notches of the explosion-proof valve to achieve corrosion protection and isolation protection for the battery cell shell and the explosion-proof valve. However, the explosion-proof valve will repeatedly deform during the preparation of the battery cell sample, and the deformation resistance stability of the insulating protective layer is challenging, and the insulating protective layer has no corrosion repair ability.

[0080] Based on the above considerations, in order to solve the problem that the composite insulating layer disposed on the inner wall surface of the battery cell shell and / or the inner surface of the explosion-proof valve (i.e., the surface of the explosion-proof valve facing the inside of the battery cell) has poor bonding strength, poor interface bonding stability, and lacks the ability to spontaneously block corrosion. After in-depth research, a composite insulating coating is proposed, including a laminated film layer and an adhesive layer, the film layer includes a dynamically cross-linked network structure formed by positively charged metal ions and negatively charged functional groups; the adhesive layer includes an organic substance containing polar functional groups, the polar functional groups in the organic substance can form chemical bonds with negatively charged functional groups in the film layer; and chemical bonds are formed at least at the interface between the film layer and the adhesive layer.

[0081] In such a composite insulating coating, there is a double-layer structure of a film layer and an adhesive layer, wherein the dynamic cross-linked network structure formed by positively charged metal ions and negatively charged functional groups in the film layer not only has high hiding properties for the electrolyte, reducing the corrosion of the electrolyte to the substrate to which the composite insulating coating is applied; and the positively charged metal ions complexed in the dynamic cross-linked network structure can act as an inhibitor. When defects occur in the composite insulating coating or the substrate, the positively charged metal ions in the film layer can be converted into insoluble metal precipitates through physical and chemical reactions and precipitate and aggregate at the defects, thereby filling the defects of the composite insulating coating and the substrate, achieving the effect of spontaneously blocking corrosion and better protecting the substrate from corrosion. In addition, the organic matter containing polar functional groups included in the adhesive layer does not react with the electrolyte, so that the adhesive layer has high electrolyte hiding power and high toughness, which can not only protect the application substrate from corrosion, but also provide stress buffering for the deformation of the application substrate, reducing the risk of deformation of the application substrate. Moreover, the polar functional groups in the organic matter can form chemical bonds with the negatively charged functional groups in the film layer; at least chemical bonds are formed at the interface between the film layer and the adhesive layer, which not only improves the bonding strength and bonding stability between the film layer and the adhesive layer, but also improves the self-healing function of the composite insulating coating, and can better ensure the stable conformality of the double-layer structure interface, thereby improving the protective effect of the composite insulating coating on the application substrate.

[0082] For ease of understanding, the present application is specifically described by the following examples. It should be understood that the following examples are only used to further illustrate the present application scheme and are not used to limit the scope of the present application.

[0083] In the first aspect, an embodiment of the present application provides a composite insulating coating, comprising a film layer and an adhesive layer arranged in a stacked manner, wherein the film layer is adhered to the surface of an application substrate, the film layer comprises an organic component with negatively charged functional groups and positively charged metal ions, and the positively charged metal ions and the negatively charged functional groups form a dynamically cross-linked network structure; the adhesive layer is arranged on the surface of the film layer, has electrolyte barrier properties, the adhesive layer comprises an organic matter containing polar functional groups, and the polar functional groups in the adhesive layer and the negatively charged functional groups in the film layer form chemical bonds at the interface.

[0084] Thus, the composite insulating coating provided in the embodiment of the present application has a double-layer structure of a film layer and an adhesive layer stacked in layers, which has at least the following advantages:

[0085] 1. The film layer includes organic components with negatively charged functional groups and positively charged metal ions. The negatively charged functional groups in the organic components can form a dynamic cross-linked network structure at the microscopic level through complexation with the positively charged metal ions. On the one hand, the composite insulating coating has high covering properties and toughness for the electrolyte, effectively reducing the corrosion of the electrolyte to the application substrate; on the other hand, the complexed positively charged metal ions in the dynamic cross-linked network structure can act as an inhibitor. When defects such as damage and gaps appear on the substrate surface and / or the composite insulating coating, the positively charged metal ions in the film layer can be converted into insoluble metal precipitates through a physicochemical reaction with an acidic or alkaline medium. The insoluble metal precipitates are continuously precipitated and aggregated at the defects, which can effectively fill the defects of the composite insulating coating and the substrate, thereby achieving a self-repairing effect on the composite insulating coating, and spontaneously blocking corrosion of the application substrate, better protecting the substrate from corrosion. In addition, the film layer including the organic component with negatively charged functional groups and the positively charged metal ions has a good bonding effect with the surface of the application substrate, and can be stably and firmly bonded to the surface of the metal substrate to protect the substrate.

[0086] 2. The bonding layer includes organic matter containing polar functional groups. The bonding layer does not react with the electrolyte and has high electrolyte barrier properties, further reducing the corrosion of the electrolyte to the application substrate. In addition, the polar functional groups of the organic matter in the bonding layer can form chemical bonds with the negatively charged functional groups in the film layer at least at the interface, which not only improves the bonding strength and bonding stability between the film layer and the bonding layer, ensures the stability of the interface between the coatings, and ensures the stability of the coating interface; but also improves the self-repairing function of the composite insulating coating, which can better ensure the stable conformality of the double-layer structure interface, thereby improving the protective effect of the composite insulating coating on the application substrate. In addition, the organic matter containing polar functional groups in the bonding layer makes the film layer have high toughness, can provide stress buffering for the deformation of the application substrate, reduce the risk of deformation of the application substrate, and further improve the application stability of the substrate.

[0087] The composite insulating coating of the embodiment of the present application is particularly suitable for battery cell housings and / or explosion-proof valves. The composite insulating coating is laminated and arranged on the inner wall of the battery cell housing and / or the inner surface of the explosion-proof valve facing the battery cell. The high electrolyte covering property, high insulation and high mechanical stability of the composite insulating coating can effectively block the long-term corrosion of the explosion-proof valve and / or the battery cell housing. The high toughness and interface self-repair function of the composite insulating coating, when applied to the inner coating of the battery cell explosion-proof valve, can improve the hidden danger of microcracks caused by uneven stress of the substrate. When applied to the inner coating of the battery cell housing, it can reduce the risk of abnormal high-voltage electrical breakdown of the substrate and improve long-term reliability. At the same time, it can participate in the preset pressure adjustment of the explosion-proof valve. Under extreme conditions, the composite insulating coating can soften and fail in advance, reduce the valve opening pressure and release the internal pressure and heat of the battery cell in time, which greatly guarantees the sealing and safety functions of the explosion-proof valve.

[0088] In some possible implementations, the structural schematic diagram of the composite insulating coating is shown in the attached Figure 1 The surface of the application substrate includes a film layer and an adhesive layer which are stacked in sequence, the film layer includes an organic component with a negatively charged functional group X and a positively charged metal ion M, the positively charged metal ion N and the negatively charged functional group X form a dynamically cross-linked network structure of M1-X-M2-X-M3-…-Mi; the adhesive layer includes an organic substance containing a polar functional group Y; at least at the interface between the film layer and the adhesive layer, the polar functional group Y in the organic substance and the negatively charged functional group X in the organic component form an XY chemical bond.

[0089] In some possible embodiments, the mass percentage of positively charged metal ions in the film layer is 1% to 30%, preferably 10% to 20%. In this case, the mass percentage of positively charged metal ions in the film layer ensures that the negatively charged functional groups in the organic components can fully complex with the positively charged metal ions to form a dynamic cross-linked network structure, ensures that the electrolyte has a covering property, fills the defects of the composite insulating coating, and has a self-repairing effect on the composite insulating coating, and has a spontaneous corrosion blocking effect on the application substrate. In addition, the content of positively charged metal ions ensures the toughness of the film layer, thereby ensuring that the film layer provides a stress buffering effect for the deformation of the application substrate, avoiding the reduction of the toughness of the film layer due to excessively high content of positively charged metal ions, and increasing the risk of easy rupture of the film layer due to mechanical deformation. Exemplarily, in the film layer, the mass percentage of the positively charged metal ions is typically but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc. In the film layer, the mass percentage of the positively charged metal ions is preferably any value or interval between 10 and 20%, such as 10 to 12%, 12 to 14%, 14 to 16%, 16 to 18%, 18 to 20%, etc.

[0090] In some possible embodiments, in the film layer, the positively charged metal ions include at least one of Cr ions, Zr ions, Ni ions, Co ions, Mo ions, Zn ions, Mn ions, V ions, and Ce ions. In this case, these positively charged metal ions in the inorganic component can fully complex with the negatively charged functional groups in the organic component to form a dynamic cross-linked network structure, forming a film layer that has a covering property for the electrolyte and has toughness; and these positively charged metal ions in the inorganic component can be converted into insoluble metal precipitates through physical and chemical reactions with acidic or alkaline media, and continuously precipitate and aggregate at the defects of the composite insulating coating, effectively filling the defects of the composite insulating coating, thereby achieving a self-repairing effect on the composite insulating coating, and realizing spontaneous corrosion blocking for the application substrate, and better protecting the substrate from corrosion. Specifically, Cr ions usually exist with a valence of +2 or +3. Under alkaline conditions, Cr ions will react with hydroxide ions (OH - ) to form an insoluble precipitate of chromium (III) hydroxide (Cr(OH)3); under acidic conditions, Cr ions react with chromate ions (CrO4 2- ) or sulfur dioxide ion (SO4 2-) to form precipitates, namely silver chromate (Ag2CrO4) or chromium sulfate (CrSO4). Zr ions usually exist with a +4 valence. Under alkaline conditions, Zr ions react with hydroxide ions (OH - ) to form an insoluble precipitate of zirconium hydroxide (Zr(OH)4); under acidic conditions, Zr ions react with tungstate ions (WO4 2- ) to produce a precipitate of zirconium tungstate (Zr(WO4)2). Ni ions usually exist in +2 valence. Under alkaline conditions, Ni ions react with hydroxide ions (OH - ) to form a precipitate of nickel hydroxide (Ni(OH)2). Co ions usually exist in +2 or +3 valence. Under alkaline conditions, Co ions react with hydroxide ions (OH - ) to form an insoluble precipitate of cobalt hydroxide (Co(OH)2); under acidic conditions, Co ions react with chloride ions (Cl - ) or nitrous acid (NO 2- ) to produce precipitates of cobalt chloride (CoCl2) or cobalt nitrite (Co(NO2)2). Mo ions usually exist with a valence of +6. Under acidic conditions, Mo ions will react with oxygenate ions to produce a precipitate of molybdenum oxide (MoO3). Zn ions usually exist with a valence of +2. Zinc is an amphoteric element. Its hydroxide is insoluble in water and has weak alkalinity and weak acidity. The chemical formula of its insoluble precipitate can be written as: basic form: Zn(OH)2, acid form: H2ZnO2. Mn ions usually exist with a valence of +2, +3, +4, +6 or +7. Under alkaline conditions, Mn ions will react with hydroxide ions (OH - ) to form an insoluble precipitate of manganese hydroxide (Mn(OH)2 or Mn(OH)3); under acidic conditions, the specific precipitate formed will be different, such as with sulfite ions (SO3 2- ) to form manganese sulfite (MnSO3). V ions usually exist in +2, +3, +4, +5 or +6 valences. Under acidic conditions, V ions react with phosphoric acid to form vanadium phosphate (VPO4) as a precipitate. There are also precipitates formed by other reactions. Ce ions usually exist in +3 or +4 valences. Under alkaline conditions, Ce ions react with hydroxide ions (OH - ) to form an insoluble precipitate of cerium hydroxide (Ce(OH)3); under acidic conditions, Ce ions react with nitrite ions (NO 2- ) reaction to produce cerium nitrite (Ce(NO2)4) as a precipitate.

[0091] In some possible embodiments, the organic component with negatively charged functional groups includes at least one of polyester, polyether, polyol, polyolefin acid, polyaldehyde, polyketone, polyamide, and polysiloxane. These organic components used in the embodiments of the present application not only do not react with the electrolyte, so that the film layer has electrolyte covering properties and toughness, which can protect the application substrate from corrosion and relieve the stress caused by substrate deformation, but also contain negatively charged functional groups. These negatively charged functional groups can be complexed with positively charged metal ions to form a dynamic cross-linked network structure, further improving the covering properties of the film layer for the electrolyte, and improving the filling effect of the film layer on coating defects, so that the composite insulating coating has a self-repairing effect, and produces a spontaneous corrosion blocking effect on the application substrate.

[0092] In some possible embodiments, the negatively charged functional group in the organic component includes an oxygen-containing functional group A. In this case, the oxygen-containing functional group in the organic component can form a complex with the positively charged metal ion, that is, a stable chemical bond is formed through a coordination bond, thereby forming a network structure of dynamic cross-linking. This complexing effect can affect the properties of the compound, and the charge and size of the positively charged metal ion and the structure, nucleophilicity and other properties of the oxygen-containing functional group will affect the strength and stability of the complexing reaction. The complexing reaction formed between the positively charged metal ion and the oxygen-containing functional group can promote the formation of dynamic cross-linking. Through chemical reactions or physical actions, the negatively charged functional groups of the organic component and the positively charged metal ions of the inorganic component are cross-linked to form a three-dimensional network structure of dynamic cross-linking. When there are a large number of organic components with oxygen-containing functional groups interacting with the positively charged metal ions of appropriate inorganic components, the coordination ability of the positively charged metal ions can connect these oxygen-containing functional groups together to form a cross-linked complex structure, thereby forming a three-dimensional network structure of dynamic cross-linking. This dynamically cross-linked network structure is often highly adjustable and controllable in the material, which makes the film layer have higher toughness, can alleviate the stress caused by the deformation of the matrix, and reduce the risk of deformation of the application matrix.

[0093] In some possible embodiments, the oxygen-containing functional group A in the organic component includes at least one of a hydroxyl group (-OH), a carboxyl group (-COOH), a carbonyl group (-C=O), an ester group (RC(=O)-O-R'), an aldehyde group (-C(=O)H), a ketone group (RC(=O)-R'), an ether group (RO-R'), and an amide group (-CO-NH2 or -CO-NH-). In the embodiments of the present application, the cross-linking and coupling effects between the oxygen-containing functional groups such as hydroxyl group (-OH), ketone group (RC(=O)-R'), ether group (RO-R'), ketone group (RC(=O)-R'), ester group (RC(=O)-O-R'), and amide group (-CO-NH2 or -CO-NH-) and the positively charged metal ions will vary depending on the characteristics of different functional groups and positively charged metal ions. Among them, the hydroxyl group (-OH) and the positively charged metal ions can usually form an alcohol sol complex, and the oxygen atom in the hydroxyl group coordinates with the positively charged metal ions to form a chemical bond. The carboxylate ion (-COO-) in the carboxyl group (-COOH) can form a complex with a positively charged metal ion. The carboxyl group (-COOH) in the carboxylic acid usually coordinates with the positively charged metal ion through the carboxylate ion to form a stable carboxylate metal salt. The carbonyl group (-C=O), as a strong polar functional group, can form a complex with a positively charged metal ion. In particular, the carbonyl group can also form a π coordination with a transition metal to form a π coordination complex, which increases the stability and selectivity of the complex reaction. The ether group (RO-R') has a relatively weak complexing effect with positively charged metal ions. The oxygen atom in the ether group can form a coordination bond with the positively charged metal ion through the lone pair of electrons with less electronegativity. However, since the ether group is not easy to break and reform the coordination bond in the solvent, the degree of cross-linking with the positively charged metal ion is relatively low. The ester group (RC(=O)-O-R') can coordinate with positively charged metal ions to form an ester sol complex, and the oxygen atom in the ester group can form a chemical bond with the positively charged metal ion through a lone pair of electrons. The aldehyde group (-C(=O)H) easily reacts with some oxidizing transition metal salts to form a cross-linked structure. For example, the aldehyde group generally reacts with transition metal citrates and permanganates with relatively high valence to generate corresponding carboxylic acids and low-valent metal ions (or single substances). In some specific embodiments, the oxygen-containing functional group A in the organic component of the film layer avoids the simultaneous presence of self-reactive functional groups, such as avoiding the simultaneous presence of two self-reactive oxygen-containing functional groups -OH and -COOH in the organic component of the film layer.

[0094] In some possible embodiments, the expression of the dynamically cross-linked network structure includes -M1-O-M2-O-…-Mi-, wherein M1, M2, and Mi are independently selected from at least one of Cr, Zr, Ni, Co, Mo, Zn, Mn, V, and Ce, and i is a positive integer greater than 2, and i represents the i-th transition metal element. In this case, the expression of the dynamically cross-linked network structure -M1-O-M2-O-…-Mi- indicates that the positively charged metal ions in the inorganic component and the oxygen-containing functional groups in the organic component form a network structure through cross-linking or chemical reaction. In some embodiments, M1, M2, and Mi in the dynamically cross-linked network structure represent transition metal elements, and M1, M2, and Mi are independently selected from one of Cr, Zr, Ni, Co, Mo, Zn, Mn, V, and Ce, respectively, wherein M1, M2, and Mi can be selected from the same transition metal element. At this time, the expression of the dynamically cross-linked network structure can be expressed as -MOMO-…-M-, or different transition metal elements can be selected to form a -M1-O-M2-O-…-Mi- structure.

[0095] In some possible implementations, the polar functional groups in the organic matter include at least one of nitrogen-containing functional groups, oxygen-containing functional groups B, and fluorine-containing functional groups. In this case, the polar functional groups such as nitrogen-containing functional groups, oxygen-containing functional groups B, and fluorine-containing functional groups in the organic matter can all be chemically bonded with the negatively charged functional groups of the organic components in the film layer through hydrogen bonds or other forms. For example, these polar functional groups in the organic matter and the oxygen-containing functional groups in the organic components can form crosslinks through hydrogen bonds. This improves the bonding strength and bonding stability between the film layer and the adhesive layer, and improves the self-repairing function of the composite insulating coating.

[0096] In some possible embodiments, the nitrogen-containing functional group includes at least one of an amide group (-CONH2), an amine group (-NH2), and an imine group (-NH-). In the organic matter of the present application embodiment, these nitrogen-containing functional groups and negatively charged functional groups can form cross-links through hydrogen bonds. Exemplarily, the amine group can form hydrogen bonds with oxygen-containing functional groups such as acid functional groups (-COOH) and alcohol functional groups (-OH).

[0097] In some possible embodiments, the oxygen-containing functional group B in the organic matter includes at least one of a hydroxyl group (-OH), a carboxyl group (-COOH), an ester group (RC(=O)-O-R'), an aldehyde group (-C(=O)H), a carbonyl group (-C=O), a ketone group (RC(=O)-R'), an ether group (RO-R'), and an amide group (-CO-NH2 or -CO-NH-). These oxygen-containing functional groups and negatively charged functional groups in the organic matter of the embodiment of the present application can form cross-links through hydrogen bonds. Specifically, the following cross-linking forms can be formed between the oxygen-containing functional group A in the organic component and the oxygen-containing functional group B in the organic matter: esterification reaction, when the carboxyl group (-COOH) and the alcohol group (-OH) undergo esterification reaction, an ester bond is formed, for example, acetic acid reacts with methanol to form methyl acetate. Acetal ketal reaction: two carbonyl (-C=O) functional groups can form acetals or ketals by sharing an oxygen atom. For example, acetaldehyde and acetone react to form 1,3-dioxopentanedione through acetal ketal reaction. In some specific embodiments, the oxygen-containing functional group B in the organic matter of the bonding layer avoids the presence of self-reactive functional groups at the same time, such as avoiding the organic matter of the bonding layer from containing two self-reactive oxygen-containing functional groups -OH and -COOH at the same time, avoiding self-reaction, and ensuring that the functional groups of the organic components in the film layer react with the functional groups of the organic matter in the bonding layer to form a stable chemical bond.

[0098] In some possible embodiments, the fluorine-containing functional group includes at least one of a fluorocarbon group and a fluorooxy group. The fluorine-containing functional group in the organic matter of the embodiment of the present application can form a chemical bond with a negatively charged functional group. Specifically, the following cross-linking forms can be formed between the fluorine-containing functional group and the oxygen-containing functional group: Nucleophilic substitution reaction: The fluorine-containing functional group can act as a nucleophilic reagent to undergo a substitution reaction with partially positively charged carbon or other atoms. For example, a trifluoromethyl (-CF3) functional group can undergo a nucleophilic substitution reaction with an alkyl halide, replacing the halogen to form a fluoroalkane. Fluorine bond, the fluorine atom in the fluorine-containing functional group can form a strong fluorine bond and form a stable bond with other atoms. This bond is usually stronger than a hydrogen bond. For example, a trifluoromethyl (-CF3) functional group can form a fluorine bond with an oxygen atom.

[0099] The polar functional groups contained in the organic matter in the bonding layer of the embodiment of the present application can form chemical bonds with the negatively charged functional groups in the film layer, such as covalent bonds, hydrogen bonds and other chemical bonding forms. In some possible embodiments, the polar functional groups in the organic matter and the negatively charged functional groups in the organic component form hydrogen bonds at the interface between the film layer and the bonding layer. In this case, the polar functional groups in the organic matter and the negatively charged functional groups in the organic component form hydrogen bonds, which can significantly improve the bonding force and bonding stability between the film layer and the bonding layer, improve the self-repairing function of the composite insulating coating, better ensure the stable conformality of the double-layer structure interface, and thus improve the protective effect of the composite insulating coating on the application substrate.

[0100] In some possible embodiments, the organic matter includes at least one of modified polyolefin, polyvinylidene fluoride, polyamide, polyimide, polyacrylonitrile, modified polyaramid, polyetheretherketone, polyethylene terephthalate, polyphenylene sulfide, and polybenzimidazole. These organic substances used in the bonding layer of the present application embodiment, on the one hand, all contain polar hydrogen-containing covalent groups or electron-rich groups such as nitrogen-containing functional groups, oxygen-containing functional groups, and fluorine-containing functional groups, and can form chemical bonds such as covalent bonds and hydrogen bonds with the negatively charged functional groups of the organic components in the film layer, thereby improving the bonding force and bonding stability between the film layer and the bonding layer, improving the coating interface stability, improving the self-repairing function of the composite insulating coating, and better ensuring the stable conformality of the double-layer structure interface, thereby improving the protective effect of the composite insulating coating on the application substrate. On the other hand, these organic substances all have good electrical insulation properties and high dielectric constants, and have good covering properties for electrolytes, thereby preventing the application substrate from being corroded by electrolytes and other media. And the film layer formed by these organic substances has high toughness, which can provide stress buffering for the deformation of the application substrate, reduce the risk of deformation of the application substrate, and further improve the application stability of the substrate. When applied to components such as battery cell shells or explosion-proof valves, it is beneficial to ensure the normal operation and safety performance of the battery. Specifically, modified polyolefins have good heat resistance, chemical corrosion resistance and mechanical properties, as well as certain electrical insulation properties and stability. They can be modified by additives to have improved electrical properties and weather resistance. Organic fluorides have excellent high temperature resistance, corrosion resistance and low surface tension, as well as flame retardant properties and excellent electrical insulation properties. They can remain stable in high temperature environments and protect the internal components of the battery. Polyethylene terephthalate (PET for short) has good mechanical properties, chemical stability and wear resistance. Polyethylene terephthalate (PET) has good electrical insulation properties and mechanical strength, which can effectively isolate the corrosion of the battery cell shell by the medium in the battery electrolyte. Polyamide has high strength, rigidity and heat resistance, as well as good chemical corrosion resistance and wear resistance, as well as excellent insulation properties, which can effectively isolate the internal electrolyte of the battery from the battery cell shell, explosion-proof valve, etc. Polyimide has excellent high temperature stability and chemical stability, as well as high mechanical strength and insulation properties, and can be used for high temperature batteries under special conditions or batteries that require high wear resistance. Polyether nitrile has excellent heat resistance, oxidation resistance and low temperature impact resistance, as well as good electrical insulation and mechanical strength. It can well protect components such as battery cell shells and explosion-proof valves, and provide stable isolation performance. The molecular weight will affect the entanglement state of the molecular chain, and the density (electrolyte resistance) and toughness of the coating will be affected, and the degree of processability will also vary.

[0101] In some possible embodiments, the molar molecular weight of the organic matter is 3000 g / mol to 300000 g / mol. Since the molecular weight of the organic matter in the bonding layer will affect the entanglement state of the molecular chain of the organic material, the coating density (electrolyte resistance) and toughness, and the degree of processability will also be affected to varying degrees. For example, the increase in molecular weight usually leads to an increase in the mechanical strength, stiffness and melting point of organic materials such as modified polyolefins, polyterephthalates, polyamides, polyimides and polyether nitrile, and the performance becomes more stable. For organic fluorides, high molecular weight usually brings better film formation performance and physical properties, such as mechanical strength, wear resistance and high temperature resistance. The molar molecular weight of the organic matter in the bonding layer of the embodiment of the present application is 3000 g / mol to 300000 g / mol, and the molecular weight has a wide range. The molar molecular weight of the organic matter can effectively ensure the covering effect, insulation performance, high toughness and other characteristics of the formed bonding layer on the electrolyte within this range. Exemplarily, the molar molecular weight of the organic matter in the bonding layer can be typically but not limited to 3000 g / mol, 4000 g / mol, 5000 g / mol, 6000 g / mol, 7000 g / mol, 8000 g / mol, 9000 g / mol, 10000 g / mol, 12000 g / mol, 15000 g / mol, 18000 g / mol, 20000 g / mol, 30000 g / mol, 40000 g / mol, 50000 g / mol, 60000 g / mol, 70000 g / mol, 80000 g / mol, 90000 g / mol, 100000 g / mol, 150000 g / mol, 200000 g / mol, 250000 g / mol, 300000 g / mol, etc. Or the molar molecular weight of the organic matter can be any value or any interval value between 3000 and 300000 g / mol, for example, 3000 g / mol to 50000 g / mol, 5000 g / mol to 10000 g / mol, 10000 g / mol to 20000 g / mol, 20000 g / mol to 50000 g / mol, 50000 g / mol to 100000 g / mol, 100000 g / mol to 150000 g / mol, 150000 g / mol to 200000 g / mol, 200000 g / mol to 250000 g / mol, 250000 g / mol to 300000 g / mol, etc.

[0102] In some possible embodiments, the thickness of the composite insulating coating is 10 μm to 1000 μm, preferably 40 μm to 500 μm. Under this thickness condition, the composite insulating coating of the embodiment of the present application can ensure the protective effect of the composite insulating coating on the battery cell housing, explosion-proof valve and other battery component application substrates, avoid electrolyte contact corrosion of the substrate, effectively block the long-term corrosion of the explosion-proof valve and / or the battery cell housing, block charge conduction, and prevent the application substrate from being electrically broken down under conditions such as abnormally high voltage. At the same time, it can participate in the preset pressure adjustment of the explosion-proof valve. Under extreme conditions, the composite insulating coating can soften and fail in advance, reduce the valve opening pressure and release the internal pressure and heat of the battery cell in time, which greatly ensures the airtightness and safety function of the explosion-proof valve. This thickness range effectively avoids the problem of reducing the battery energy density due to the excessive proportion of the composite insulating coating in the application system such as the battery cell. Exemplarily, the thickness of the composite insulating coating may be typically but not limited to 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, etc. Or the thickness of the composite insulating coating is preferably any value or interval between 40μm and 500μm, for example, 40μm to 100μm, 100μm to 150μm, 150μm to 200μm, 200μm to 250μm, 250μm to 300μm, 300μm to 350μm, 350μm to 400μm, 400μm to 450μm, 450μm to 500μm, etc.

[0103] In some possible embodiments, the thickness of the film layer is 5 μm to 500 μm, preferably 20 μm to 250 μm. Under this thickness condition, the film layer in the composite insulating coating of the embodiment of the present application ensures high covering properties and toughness for the electrolyte, reduces the corrosion of the electrolyte to the application substrate, and ensures that the positively charged metal ions complexed in the network structure can be converted into insoluble metal precipitates by physical and chemical reactions with acidic or alkaline media, and continuously precipitate and aggregate at defects, ensuring the filling effect of defects in the composite insulating coating, ensuring the self-repair effect of the composite insulating coating, and the spontaneous corrosion blocking effect on the application substrate. Exemplarily, the thickness of the film layer can be 5 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 400 μm, 500 μm, etc. Alternatively, the thickness of the film layer is preferably any value or interval between 20μm and 250μm, such as 20μm to 30μm, 30μm to 50μm, 50μm to 80μm, 80μm to 100μm, 100μm to 130μm, 130μm to 150μm, 150μm to 180μm, 180μm to 200μm, 200μm to 230μm, 230μm to 250μm, etc.

[0104] In some possible embodiments, the thickness of the bonding layer is 5 μm to 500 μm, preferably 20 μm to 250 μm. Under this thickness condition, the bonding layer in the composite insulating coating of the embodiment of the present application ensures high covering properties of the electrolyte and reduces the corrosion of the electrolyte to the application substrate. At the same time, it ensures that the polar functional groups of the organic matter in the bonding layer can form a dynamic cross-linked chemical bond with the negatively charged functional groups in the film layer at least at the interface between the film layer and the bonding layer, ensuring the bonding force and bonding stability between the film layer and the bonding layer, improving the self-repairing function of the composite insulating coating, and improving the protective effect of the composite insulating coating on the application substrate. Exemplarily, the thickness of the bonding layer is typically but not restrictive, and can be 5 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 400 μm, 500 μm, etc. Alternatively, the thickness of the bonding layer is preferably any value or range between 20μm and 250μm, such as 20μm to 30μm, 30μm to 50μm, 50μm to 80μm, 80μm to 100μm, 100μm to 130μm, 130μm to 150μm, 150μm to 180μm, 180μm to 200μm, 200μm to 230μm, 230μm to 250μm, etc.

[0105] In some embodiments, the thickness of the composite insulating coating is 40 μm to 500 μm, wherein the thickness of the film layer is 20 μm to 250 μm, and the thickness of the adhesive layer is 20 μm to 250 μm.

[0106] In some possible implementations, the surface density of the composite insulating coating is 0.5 mg / m 2 ~50 mg / m 2 , preferably 1 mg / m 2 ~20 mg / m 2 . The surface density condition of the composite insulating coating in the embodiment of the present application ensures the covering property of the composite insulating coating on the electrolyte, and the effect of providing stress buffering for the deformation of the application substrate, while ensuring the defect filling effect of the composite insulating coating, the self-repair effect of the composite insulating coating, and the spontaneous corrosion blocking effect on the application substrate. When the composite insulating coating is applied to components such as battery cell housings or explosion-proof valves, it is helpful to ensure the normal operation and safety performance of the battery. Exemplarily, the surface density of the composite insulating coating can be typically but not limitatively 0.5 mg / m 2 , 1mg / m 2 , 2mg / m 2 , 4mg / m 2 , 6mg / m 2 , 8mg / m 2 , 10mg / m 2 , 12mg / m 2 , 14mg / m 2 , 16mg / m 2 , 18mg / m 2 , 20mg / m 2 , 30mg / m 2 , 40mg / m 2 , 50mg / m 2 Or the surface density of the composite insulating coating is preferably 1 mg / m 2 ~20 mg / m 2 Any value or interval between, such as 1mg / m 2 ~2 mg / m 2 2-4 mg / m 2 4-6 mg / m 2 , 6-8 mg / m 2 8-10 mg / m 2 10-12 mg / m 2 12-15 mg / m 2 15-18 mg / m 2 18-20 mg / m 2 wait.

[0107] In some possible embodiments, the dielectric strength of the composite insulating coating is not less than 5000V / mm, preferably not less than 10000V / mm. The maximum voltage per unit millimeter thickness of the composite insulating coating of the embodiment of the present application is not less than 5000V / mm, and has high dielectric strength, indicating that the composite insulating coating has good insulation performance, can resist high voltage without dielectric breakdown, and can effectively avoid the composite insulating coating from being electrically broken down. The composite insulating coating with high dielectric strength is applied to components such as battery cell housings and explosion-proof valves, which can not only effectively block the long-term corrosion of explosion-proof valves and / or battery cell housings, improve the hidden dangers of microcracks caused by uneven stress of battery cell housings and / or explosion-proof valves, but also reduce the risk of leakage caused by abnormal high-voltage electrical breakdown of battery cell housings and explosion-proof valves, and improve long-term reliability. At the same time, it can participate in the preset pressure adjustment of the explosion-proof valve. Under extreme conditions, the composite insulating coating can soften and fail in advance, reduce the valve opening pressure, and release the internal pressure and heat of the battery cell in time, which greatly guarantees the airtightness and safety functions of the explosion-proof valve. Exemplarily, the dielectric strength of the composite insulating coating may be typically but not limited to 5000 V / mm to 6000 V / mm, 6000 V / mm to 7000 V / mm, 7000 V / mm to 8000 V / mm, 8000 V / mm to 10000 V / mm, 10000 V / mm to 12000 V / mm, 12000 V / mm to 15000 V / mm, 15000 V / mm to 18000 V / mm, 18000 V / mm to 20000 V / mm, 20000 V / mm to 2 5000V / mm, 25000V / mm~30000V / mm, 30000V / mm~35000V / mm, 35000V / mm~40000V / mm, 40000V / mm~50000V / mm, 50000V / mm~60000V / mm, 60000V / mm~70000V / mm, 70000V / mm~80000V / mm, 80000V / mm~90000V / mm, 90000V / mm~100000V / mm, etc.

[0108] In some possible embodiments, the softening temperature of the composite insulating coating is 70°C to 250°C, preferably 90°C to 200°C. Under this softening temperature condition, the composite insulating coating has a higher softening temperature, ensuring that the composite insulating coating protects the substrate to operate safely during normal operation. When under extreme conditions, the composite insulating coating can soften and fail in advance, such as participating in the preset pressure adjustment of the explosion-proof valve through softening, reducing the valve opening pressure and releasing the internal pressure and heat of the battery cell in time, which greatly ensures the airtightness and safety function of the explosion-proof valve. Exemplarily, the softening temperature of the composite insulating coating can be typically but not limitatively 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc. Alternatively, the softening temperature of the composite insulating coating is preferably any value or interval between 90°C and 200°C, such as 90-100°C, 100-110°C, 110-120°C, 120-130°C, 130-140°C, 140-150°C, 150-160°C, 160-170°C, 170-180°C, 180-190°C, 190-200°C, etc.

[0109] In some possible implementations, the thickness of the composite insulating coating is 40 μm to 500 μm, wherein the thickness of the film layer is 20 μm to 250 μm, the thickness of the bonding layer is 20 μm to 250 μm, and the surface density of the composite insulating coating is 1 mg / m 2 ~20 mg / m 2 , the dielectric strength is not less than 10000V / mm, and the softening temperature is 90~150℃. In this case, the composite insulating coating can effectively block the corrosion of the electrolyte to the substrate through the synergistic closed electrolyte effect of the inner and outer double-layer structure on the surface of the application substrate, and form a dense high-resistivity insulating "fortress" on the surface of the application substrate to avoid abnormal electrical breakdown. In addition, the positively charged metal ions in the dynamic cross-linked network structure formed by the positively charged metal ions and the negatively charged functional groups in the film layer generate insoluble compounds through cathode reaction and then precipitate, filling or even eliminating corrosion sites and blocking corrosion. The chemical bonding formed by the polar functional groups in the synergistic bonding layer and the negatively charged functional groups in the film layer enables the composite insulating coating to have a cross-linking self-repairing function, better guarantee the stable conformality of the double-layer structure interface, and improve the protective effect of the composite insulating coating on the application substrate. In addition, through the double-layer adjustment of the thickness and softening temperature of the composite insulating coating, it can better participate in the preset pressure adjustment together with the explosion-proof valve notch, and the composite insulating coating can soften and reduce the valve opening pressure under extreme conditions.

[0110] The composite insulating coating in the above embodiments of the present application can be prepared by the following embodiment method.

[0111] Second, as attached Figure 2 As shown, the embodiment of the present application provides a method for preparing a composite insulating coating, comprising the following steps:

[0112] S10. After preparing a mixed slurry comprising an organic component having a negatively charged functional group and a metal component having a positively charged metal ion, the mixed slurry is formed into a film layer on the surface of the application substrate to form a film layer; in the film layer, the positively charged metal ions and the negatively charged functional groups form a dynamic cross-linked network structure;

[0113] S20. Form an organic substance containing polar functional groups into a film layer on the surface of the film layer to form an adhesive layer with electrolyte barrier properties to obtain a composite insulating coating; at the interface between the film layer and the adhesive layer, the polar functional groups in the adhesive layer form chemical bonds with the negatively charged functional groups in the film layer.

[0114] The method for preparing the composite insulating coating of the embodiment of the present application is to prepare a mixed slurry including an organic component with negatively charged functional groups and a metal component with positively charged metal ions, and then make the mixed slurry into a film layer on the surface of the application substrate, so that the negatively charged functional groups in the organic component and the positively charged metal ions in the inorganic component form a dynamic cross-linked network structure at the microscopic level through complexation. Organic matter containing polar functional groups is made into a film layer on the surface of the film layer, so that the polar functional groups in the organic matter and the negatively charged functional groups in the organic components of the film layer form chemical bonds, thereby forming a stable bonding layer on the surface of the film layer to obtain a composite insulating coating. The preparation process is simple and suitable for large-scale industrial production and application. The film layer in the prepared composite insulating coating has high covering properties and toughness for the electrolyte, can cooperate to seal the electrolyte, has high mechanical stability, and effectively reduces the corrosion of the electrolyte to the application substrate; and the positively charged metal ions can be converted into insoluble metal precipitates through physical and chemical reactions with acidic or alkaline media, which are continuously precipitated and aggregated, effectively filling the defects of the composite insulating coating and the substrate, achieving a self-repairing effect on the composite insulating coating, and spontaneously blocking corrosion on the application substrate, better protecting the substrate from corrosion. In addition, the bonding layer is arranged on the surface of the film layer, and the organic matter containing polar functional groups can form chemical bonds with the negatively charged functional groups in the organic components of the film layer at the interface, thereby improving the bonding force and bonding stability between the film layer and the bonding layer, ensuring the stability of the coating interface, improving the self-repairing function of the composite insulating coating, better ensuring the stable conformality of the double-layer structure interface, and improving the protective effect of the composite insulating coating on the application substrate. In addition, the composite insulating coating has high toughness and high insulation, which can reduce the risk of deformation of the application substrate and the risk of abnormal high-voltage electrical breakdown, and improve the application stability of the substrate.

[0115] In the above step S10, the preparation of the film layer includes the following steps:

[0116] S11. Dissolve the organic component with negatively charged functional groups in a first solvent to obtain a first solution. In some embodiments, the organic component with negatively charged functional groups can be directly purchased commercially or prepared by physical blending / chemical grafting modification.

[0117] S12. Dissolve the metal component with positively charged metal ions in the second solvent to obtain a second solution. In some embodiments, the metal component with positively charged metal ions can be directly purchased commercially.

[0118] S13. After the first solution and the second solution are mixed, washed, extracted, and a polymer complexed with metal ions is obtained;

[0119] S14. After dissolving the polymer complexing the metal ions in an organic solvent, a film layer is formed on the surface of the application substrate to obtain a film layer.

[0120] In this case, a first solution of an organic component with negatively charged functional groups and a second solution of a metal component with positively charged metal ions are prepared separately, and then the first solution and the second solution are mixed to prepare a mixed slurry including an organic component with negatively charged functional groups and a metal component with positively charged metal ions. The negatively charged functional groups in the organic component of the mixed slurry can complex with the positively charged metal ions to form a dynamically cross-linked network structure during the film formation process. On the one hand, the composite insulating coating has high covering properties and toughness for the electrolyte, effectively reducing the corrosion of the electrolyte on the application substrate; on the other hand, the positively charged metal ions complexed in the dynamically cross-linked network structure can act as an inhibitor. When the composite insulating coating on the surface of the substrate has defects such as damage and gaps, the positively charged metal ions in the film layer can be converted into insoluble metal precipitates through a physicochemical reaction with an acidic or alkaline medium. The insoluble metal precipitates continuously precipitate and aggregate at the defects, which can effectively fill the defects of the composite insulating coating, thereby achieving a self-repairing effect on the composite insulating coating, spontaneously blocking corrosion of the application substrate, and better protecting the substrate from corrosion.

[0121] In some embodiments, after the mixed slurry is washed with deionized water to remove organic / inorganic anions, an extractant is added for extraction to obtain a polymer complexing metal ions; the polymer complexing metal ions is then dissolved in an organic solvent, and a film layer is prepared on the surface of the application substrate by spraying or casting.

[0122] In some possible embodiments, the metal component includes an organic metal salt and / or an inorganic metal salt. In this case, the metal component with positively charged metal ions can be in the form of an inorganic metal salt and / or an organic metal salt. The positively charged metal ions in the metal salt are easily dissociated and fully complexed with the negatively charged functional groups in the organic component to form a dynamic cross-linked network structure, ensuring the covering properties of the film layer on the electrolyte and the defect filling effect of the film layer, so that the composite insulating coating has a self-repairing effect and produces a spontaneous corrosion blocking effect on the application substrate. In some embodiments, the metal component includes a soluble organic metal salt and / or an inorganic metal salt. A soluble inorganic metal salt refers to an inorganic compound that can be completely dissolved in water or other solvents. Common types of soluble inorganic metal salts include: chlorides, sulfates, nitrates, sulfites, carbonates, acetates, etc. Soluble organic metal salts refer to organic metal complexes formed with organic acids as ligands, compounds that can be completely dissolved in water or other solvents. Common types of soluble organic metal salts include: acetates, oxalates, tartrates, etc.

[0123] In some possible embodiments, the metal component of the positively charged metal ion includes at least one of a soluble inorganic metal salt and / or an organic metal salt. In some possible embodiments, the positively charged metal ion in the inorganic component includes at least one of Cr ions, Zr ions, Ni ions, Co ions, Mo ions, Zn ions, Mn ions, V ions, and Ce ions. At this time, the positively charged metal ion can specifically be a Cr salt, and its soluble inorganic Cr salt includes chromium chloride (CrCl2, CrCl3), chromium sulfate (CrSO4), chromium nitrate (Cr(NO3)3), etc. Soluble organic Cr salts include chromium acetate (Cr(C2H3O2)2), etc. Zr salts, and its soluble inorganic Zr salts include zirconium chloride (ZrCl4), zirconium sulfate (ZrSO4), etc. Ni salts, including soluble inorganic Ni salts, include nickel chloride (NiCl2, NiCl3), nickel sulfate (NiSO4), nickel nitrate (Ni(NO3)2), etc., and soluble organic Ni salts include nickel acetate (Ni(C2H3O2)2), etc. Co salts, including soluble inorganic Co salts, include cobalt chloride (CoCl2, CoCl3), cobalt sulfate (CoSO4), cobalt nitrate (Co(NO3)2), etc., and soluble organic metal salts include cobalt acetate (Co(C2H3O2)2), etc. Mo salts, including soluble inorganic Mo salts, include molybdenum chloride (MoCl2, MoCl3), molybdenum sulfate (MoSO4), etc. Zn salts, including soluble inorganic Zn salts, include zinc chloride (ZnCl2), zinc sulfate (ZnSO4), zinc nitrate (Zn(NO3)2), etc. Mn salts, including soluble inorganic Mn salts, include manganese chloride (MnCl2, MnCl3), manganese sulfate (MnSO4), manganese nitrate (Mn(NO3)2), etc., and soluble organic Mn salts include manganese acetate (Mn(C2H3O2)2), etc. V salts, including soluble inorganic V salts, include vanadium chloride (VCl2, VCl3), vanadium sulfate (VSO4), vanadium nitrate (V(NO3)3), etc. Ce salts, including soluble inorganic Ce salts, include cerium chloride (CeCl3), cerium sulfate (CeSO4), etc.

[0124] In some possible embodiments, the organic component includes at least one of polyester, polyether, polyol, polyolefin acid, polyaldehyde, polyketone, polyamide, and polysiloxane. The organic components with negatively charged functional groups do not react with the electrolyte, so that the film layer has electrolyte covering properties and toughness, which can protect the application substrate from corrosion and relieve the stress caused by substrate deformation, and these negatively charged functional groups can form a dynamic cross-linked network structure with positively charged metal ions, further improving the covering properties of the film layer for the electrolyte, and improving the film layer's effect of filling coating defects, so that the composite insulating coating has a self-repairing effect, and produces a spontaneous corrosion blocking effect on the application substrate.

[0125] In some possible embodiments, the first solvent and / or the second solvent are independently selected from at least one of a polar solvent, a dipolar solvent, and a non-polar solvent. These solvents have good solubility for organic components with negatively charged functional groups and metal components with positively charged metal ions. Among them, polar solvents refer to solvents containing polar groups such as hydroxyl (-OH) or carbonyl (-C=O), such as water, formamide, ethanol, glycerol, propylene glycol, etc. The positive and negative centers of gravity of the molecules of these solvents do not overlap, resulting in polarity of the molecules. For polar solvents, the two physical quantities used to characterize the size of the molecular polarity are the dipole moment and the dielectric constant. The larger the dielectric constant, the greater its polarity. A dipolar solvent is a solvent containing a polar group in the molecule, but the dipole moment of the entire molecule is zero. The dielectric constant of this type of solvent is relatively small and belongs to a medium polar solvent. Common dipolar solvents include dimethyl sulfoxide (DMSO), dimethylformamide (DMF), acetone, acetonitrile (CH3CN), dimethylacetamide (DMAC) and hexamethylphosphoramide (HMP). Non-polar solvents are solvents composed of non-polar molecular solutions. Non-polar molecules are mostly composed of covalent bonds and have no electrons or very low electron activity. Commonly used non-polar solvents include benzene, liquid paraffin, chloroform, ether, carbon tetrahalide, gasoline, etc. This type of solvent neither undergoes proton self-transfer reaction nor undergoes solvation with the solute.

[0126] In some possible implementations, the mass percentage of positively charged metal ions in the film layer is 10-20%. In this case, the mass percentage of positively charged metal ions in the film layer ensures that the negatively charged functional groups in the organic component can fully complex with the positively charged metal ions to form a dynamic cross-linked network structure, ensuring the covering property of the electrolyte, the defect filling effect of the composite insulating coating, the self-repair effect of the composite insulating coating, and the spontaneous corrosion blocking effect on the application substrate.

[0127] In some possible embodiments, the positively charged metal ions in the metal component include at least one of Cr ions, Zr ions, Ni ions, Co ions, Mo ions, Zn ions, Mn ions, V ions, and Ce ions. In this case, these positively charged metal ions in the inorganic component can fully complex with the negatively charged functional groups in the organic component to form a dynamic cross-linked network structure, forming a film layer with a covering property and toughness for the electrolyte; and these positively charged metal ions in the inorganic component can be converted into insoluble metal precipitates by a physicochemical reaction with an acidic or alkaline medium, and continuously precipitate and aggregate at the defects of the composite insulating coating, effectively filling the defects of the composite insulating coating, thereby achieving a self-repairing effect on the composite insulating coating, achieving spontaneous corrosion blocking for the application substrate, and better protecting the substrate from corrosion.

[0128] In some possible embodiments, the negatively charged functional group in the organic component includes an oxygen-containing functional group A. In some possible embodiments, the oxygen-containing functional group A includes at least one of a hydroxyl group (-OH), a carboxyl group (-COOH), a carbonyl group (-C=O), an ester group (RC(=O)-O-R'), an aldehyde group (-C(=O)H), a ketone group (RC(=O)-R'), an ether group (RO-R'), and an amide group (-CO-NH2 or -CO-NH-). In this case, these oxygen-containing functional groups in the organic component can form a complex with the positively charged metal ions, that is, a stable chemical bond is formed through a coordination bond, thereby forming a dynamically cross-linked network structure. In some possible embodiments, the expression of the dynamically cross-linked network structure includes -M1-O-M2-O-...-Mi-, wherein M1, M2, and Mi are independently selected from at least one of Cr, Zr, Ni, Co, Mo, Zn, Mn, V, and Ce, and i is a positive integer greater than 2, and i represents the i-th transition metal element.

[0129] In the above step S20, the preparation of the bonding layer includes the steps of:

[0130] S21. After the organic matter containing polar functional groups is prepared into a film layer of a preset morphology, it is compounded to the surface of the film layer by hot pressing to obtain a bonding layer. In some embodiments, after the commercially available or prepared organic matter containing polar functional groups is pre-made into a film layer of a preset shape and size, the film layer is compounded on the film layer by hot pressing to obtain a bonding layer.

[0131] Alternatively, S22. After the organic matter containing polar functional groups is made into an insulating slurry, the insulating slurry is deposited on the surface of the film layer and dried to obtain a bonding layer. In this case, during the drying process of the insulating slurry deposited on the surface of the film layer, the polar functional groups in the organic matter of the insulating slurry can better form chemical bonds with the negatively charged functional groups in the film layer, at least forming chemical bonds at the interface between the film layer and the bonding layer, which not only improves the bonding force and bonding stability between the film layer and the bonding layer, but also improves the self-repairing function of the composite insulating coating, and can better ensure the stable conformality of the interface of the double-layer structure, thereby improving the protective effect of the composite insulating coating on the application substrate. In addition, the organic matter containing polar functional groups in the bonding layer makes the film layer have high toughness, which can provide stress buffering for the deformation of the application substrate, reduce the risk of deformation of the application substrate, and further improve the application stability of the substrate.

[0132] In some possible embodiments, the polar functional group in the organic matter includes at least one of a nitrogen-containing functional group, an oxygen-containing functional group B, and a fluorine-containing functional group. In some possible embodiments, the nitrogen-containing functional group includes at least one of an amide group (-CONH2), an amine group (-NH2), and an imine group (-NH-). In some possible embodiments, the oxygen-containing functional group B includes at least one of a hydroxyl group (-OH), a carboxyl group (-COOH), an ester group (RC(=O)-O-R'), an aldehyde group (-C(=O)H), a carbonyl group (-C=O), a ketone group (RC(=O)-R'), an ether group (RO-R'), and an amide group (-CO-NH2 or -CO-NH-). In some possible embodiments, the fluorine-containing functional group includes at least one of a fluorocarbon group and a fluorooxy group (-F). In this case, polar functional groups such as nitrogen-containing functional groups, oxygen-containing functional groups B, and fluorine-containing functional groups in the organic matter can all chemically bond with negatively charged functional groups of the organic components in the film layer through hydrogen bonds and other forms.

[0133] In some possible embodiments, the organic matter includes at least one of modified polyolefin, polyvinylidene fluoride, polyamide, polyimide, polyacrylonitrile, modified polyaramid, polyetheretherketone, polyethylene terephthalate, polyphenylene sulfide, and polybenzimidazole. These organic substances used in the bonding layer of the embodiment of the present application all contain polar functional groups, which can form chemical bonds such as covalent bonds and hydrogen bonds with the negatively charged functional groups of the organic components in the film layer, thereby improving the bonding force and bonding stability between the film layer and the bonding layer, improving the self-repairing function of the composite insulating coating, and better ensuring the stable conformality of the interface of the double-layer structure, thereby improving the protective effect of the composite insulating coating on the application substrate. These organic substances all have good electrical insulation properties, good covering properties for electrolytes, and avoid corrosion of the application substrate by electrolytes and other media. The formed film layer has high toughness, can provide stress buffering for the deformation of the application substrate, reduce the risk of deformation of the application substrate, and improve the application stability of the substrate.

[0134] In some possible embodiments, the thickness of the prepared composite insulating coating is 10 μm to 1000 μm, preferably 40 μm to 500 μm, wherein the thickness of the film layer is 5 μm to 500 μm, preferably 20 μm to 250 μm, the thickness of the bonding layer is 5 μm to 500 μm, preferably 20 μm to 250 μm, and the surface density of the composite insulating coating is 1 mg / m 2 ~20 mg / m 2, the dielectric strength is not less than 10000V / mm, and the softening temperature is 70℃~250℃, preferably 90℃~200℃. In this case, the composite insulating coating can effectively block the corrosion of the electrolyte to the substrate through the synergistic closed electrolyte effect of the inner and outer double-layer structure on the surface of the application substrate, and form a dense high-resistivity insulating "fortress" on the surface of the application substrate to avoid abnormal electrical breakdown. In addition, the positively charged metal ions in the dynamic cross-linked network structure formed by the positively charged metal ions and the negatively charged functional groups in the film layer generate insoluble compounds through cathodic reactions and then precipitate, filling or even eliminating corrosion sites and blocking corrosion. The chemical bonding formed by the polar functional groups in the synergistic bonding layer and the negatively charged functional groups in the film layer enables the composite insulating coating to have a cross-linking self-repairing function, better ensure the stable conformality of the double-layer structure interface, and improve the protective effect of the composite insulating coating on the application substrate. In addition, through double-layer adjustment of the thickness and softening temperature of the composite insulating coating, it can better participate in the preset pressure adjustment together with the explosion-proof valve notch. Under extreme conditions, the composite insulating coating can soften and reduce the valve opening pressure.

[0135] In a third aspect, an embodiment of the present application provides a battery cell, which includes a battery pole core, a battery cell shell and a cover assembly, the cover assembly includes an explosion-proof valve, and the above-mentioned composite insulating coating, or the composite insulating coating prepared by the above-mentioned method, is provided at least on the inner wall surface of the battery cell shell and / or the inner surface of the explosion-proof valve.

[0136] The inner wall surface of the battery cell shell in the battery cell of the embodiment of the present application (that is, the inner wall surface of the cavity of the battery cell shell for accommodating the battery pole core is the inner wall surface) and / or the inner surface of the explosion-proof valve (that is, the surface of the explosion-proof valve facing the battery pole core is the inner surface) is provided with the above-mentioned composite insulating coating, which includes a double-layer structure of a laminated film layer and an adhesive layer, wherein the film layer is attached to the inner wall surface of the battery cell shell and / or the inner surface of the explosion-proof valve, and the adhesive layer faces the battery pole core. The composite insulating coating has high electrolyte covering properties and stability, and can effectively block the long-term corrosion of the explosion-proof valve and / or the battery cell shell. At the same time, the composite insulating coating has high insulation, high toughness and self-repairing function, which can effectively improve the hidden danger of microcracks caused by uneven stress of the battery cell shell and / or the explosion-proof valve, reduce the risk of leakage caused by abnormal high-voltage electrical breakdown of the battery cell shell and / or the explosion-proof valve, and improve long-term reliability. In addition, the composite insulating coating can participate in the preset pressure adjustment of the explosion-proof valve. Under extreme conditions, the composite insulating coating can soften and fail in advance, reduce the valve opening pressure and release the internal pressure and heat of the battery cell in time, which greatly ensures the sealing and safety function of the explosion-proof valve. Therefore, through the application of the composite insulating coating, the safety, stability, service life and other performance of the battery cell are significantly improved, giving the battery cell a better and wider application prospect.

[0137] In some possible implementations, the structural explosion diagram of the battery cell is shown in the attached figure. Figure 3 As shown, from the inside to the outside, it includes a battery core and a battery cell shell, as well as a cover assembly on the top, and the cover assembly includes an explosion-proof valve.

[0138] In some embodiments, a composite insulating coating is provided on the inner wall surface of the battery shell of the battery cell, such as Figure 4 shown.

[0139] In some embodiments, the explosion-proof valve of the battery cell is provided with notches, and a composite insulating coating is provided on the inner surface of the explosion-proof valve (i.e., the surface of the explosion-proof valve facing the inside of the battery core). The structural explosion diagram of the explosion-proof valve is shown in the attached figure. Figure 5 shown.

[0140] The embodiments of the present application do not specifically limit the positive electrode sheet, negative electrode sheet, electrolyte, separator, etc. in the battery cell and can be applied to any battery system.

[0141] In some possible implementations, the negative electrode material in the battery cell can be typically but not limitedly carbon materials such as graphite, soft carbon (such as coke), hard carbon, or nitrides, tin-based oxides, tin-based oxides, tin alloys, and silicon-based negative electrode materials.

[0142] In some possible implementations, the preparation steps of the negative electrode sheet include but are not limited to: mixing the negative electrode material with a conductive agent such as conductive carbon black, a binder such as carboxymethyl cellulose and styrene-butadiene rubber, and a solvent such as water in a mass ratio of (80-99):(1-5):(2-10):100 to form a positive electrode mixed slurry, vacuum degassing, discharging, coating on a coater, and obtaining a negative electrode sheet after rolling, slitting, and die-cutting.

[0143] In some possible implementations, the cathode material in the battery cell may be typically but not limitedly metal oxides, such as lithium cobalt oxide, lithium nickel oxide, nickel cobalt manganese ternary material, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based material, lithium manganate, lithium nickel manganate, ferroferric oxide, lithium vanadate, etc. Or polyanion salts such as phosphates, silicates, sulfates, borates, titanates, such as lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium nickel phosphate, lithium iron silicate, lithium fluorosulfate, lithium iron borate, lithium iron titanate, etc. Or fluorides, sulfides, selenides, etc., such as iron trifluoride, cobalt trifluoride, nickel trifluoride (NiF3), titanium disulfide, iron disulfide, molybdenum disulfide, niobium triselenide, etc.

[0144] In some possible implementations, the preparation steps of the positive electrode sheet include but are not limited to: mixing the positive electrode material with a conductive agent such as conductive carbon black, a binder such as polyvinylidene fluoride, and a solvent such as N-methylpyrrolidone in a mass ratio of (80-99):(1-5):(2-10):100 to form a positive electrode mixed slurry, vacuum degassing, discharging, coating on a coater, and obtaining a positive electrode sheet after rolling, slitting, and die-cutting.

[0145] In some possible implementations, the separator in the battery cell can typically but not limitatively be at least one material selected from polypropylene fiber, polyacrylonitrile fiber, polyvinyl formal fiber, poly(ethylene terephthalate), polyethylene terephthalate, polyamide fiber, and poly(p-phenylene terephthalamide).

[0146] In some possible implementations, the electrolyte in the battery cell includes at least one soluble metal salt. In some specific embodiments, the soluble metal salt includes LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], Li[(FSO2)2N], Li[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein m and n are natural numbers. These soluble metal salts can ensure high ionic conductivity of the electrolyte, and do not cause harmful side reactions with electrode materials, electrolytes, diaphragms, etc., and have good chemical stability.

[0147] In some possible implementations, the battery cell types include lithium-ion batteries, as well as new batteries such as sodium-ion batteries and lithium-air batteries.

[0148] In a fourth aspect, an embodiment of the present application provides a battery module, which includes a plurality of the above-mentioned battery cells.

[0149] The battery module provided in the embodiment of the present application includes the battery cells with high safety factor, good stability and excellent electrochemical performance, thus improving the safety performance and electrochemical performance of the battery module.

[0150] In a possible implementation, the battery module may further include a housing having a storage space, wherein a plurality of battery cells are stored in the storage space. In the above embodiment, the battery cells may be assembled into a battery module, and the number of battery cells contained in the battery module may be multiple, and the specific number may be adjusted according to the application and capacity of the battery module.

[0151] In a possible implementation, a schematic diagram of a battery module structure explosion is shown in the attached figure. Figure 6As shown, it includes a battery cell assembly, a support frame (module housing), a left side panel and a right side panel, a battery cell sampling harness and a conductive connecting plate, and a cover plate structure.

[0152] In a fifth aspect, an embodiment of the present application provides a battery pack, which includes a plurality of the above-mentioned battery modules.

[0153] The battery pack provided in the embodiment of the present application includes the battery module with high safety performance and electrochemical performance, so the battery pack also has excellent safety performance and electrochemical performance.

[0154] In a possible implementation, the battery modules in the above embodiments may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0155] In a sixth aspect, an embodiment of the present application provides an electrical device, which includes the above-mentioned battery cell, or the above-mentioned battery module, or the above-mentioned battery pack.

[0156] The electrical equipment provided in the embodiments of the present application improves the electrical safety, stability and other performances of the electrical equipment by adopting the battery cells with high safety factor, good stability and excellent electrochemical performance of the above embodiments, or the battery modules or battery packs with excellent safety performance and electrochemical performance of the above embodiments.

[0157] In a possible implementation, the electrical equipment can select the above-mentioned battery cells, battery modules or battery packs according to its usage requirements.

[0158] In one possible implementation, the electrical device may be, but is not limited to, a mobile device, such as a mobile phone, a laptop computer, etc., or an electric vehicle, such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., or an electric train, a ship and a satellite, an energy storage system, etc.

[0159] In some specific embodiments, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of such electric devices for high power and high energy density of batteries, the above-mentioned battery pack or battery module may be used.

[0160] In other specific embodiments, the electrical device may be a recorder, a radio, an electronic learning machine, a mobile phone, a tablet computer, a laptop computer, etc. Such electrical devices are usually required to be light and thin, and the battery cell in the above embodiment may be used as a power source.

[0161] Example

[0162] The following is explained in conjunction with specific embodiments. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0163] Example 1

[0164] An embodiment of the present application provides a composite insulating coating, comprising a laminated film layer and an adhesive layer, wherein the film layer has a thickness of 20 μm, comprises an organic component polyvinyl alcohol (PVA) with oxygen-containing functional groups and positively charged metal Cr ions, forms a Cr-O-Cr-O-Cr network structure in the film layer, and the mass percentage of Cr ions in the film layer is 15%; the adhesive layer has a thickness of 20 μm, comprises an organic polyimide (PI) containing polar functional groups, and has a molar molecular weight of 100,000 g / mol, and at the interface between the film layer and the adhesive layer, the polar functional groups in the organic matter and the negatively charged functional groups in the organic component form hydrogen bonds.

[0165] Its preparation comprises the following steps:

[0166] ① Dissolve polyvinyl alcohol in an appropriate amount of aqueous solution to obtain solution A;

[0167] ② Dissolve chromium trichloride in an appropriate amount of aqueous solution to obtain solution B;

[0168] ③ After mixing solution A and solution B, stir at room temperature for a certain period of time to allow Cr ions to form a complex with polyvinyl alcohol, and then wash and extract with petroleum ether to obtain a polyvinyl alcohol complex with complexed Cr ions;

[0169] ④ Dissolve the polyvinyl alcohol complex complexed with Cr ions in an appropriate amount of water and spray it on the surface of the Al metal substrate, and form a film layer on the surface of the metal substrate after drying;

[0170] ⑤ Dissolve polyimide in an appropriate amount of N-methylpyrrolidone NMP solvent and spray it on the surface of the film layer formed on the surface of the metal substrate. After drying, an adhesive layer is formed on the surface of the film layer, thereby obtaining a composite insulating coating on the surface of the metal substrate. The upper layer of the composite insulating coating is a polyimide coating, and the lower layer is a polyvinyl alcohol coating complexed with Cr ions.

[0171] Example 2

[0172] The embodiment of the present application provides a composite insulating coating, which differs from the embodiment 1 in that the positively charged metal ions in the film layer are Zr ions. Accordingly, the metal salt used in the preparation process is zirconium chloride.

[0173] Example 3

[0174] The embodiment of the present application provides a composite insulating coating, which differs from the embodiment 1 in that the positively charged metal ions in the film layer are Ni ions. Accordingly, the metal salt used in the preparation process is nickel chloride.

[0175] Example 4

[0176] The embodiment of the present application provides a composite insulating coating, which differs from the embodiment 1 in that the positively charged metal ions in the film layer are Co ions. Accordingly, the metal salt used in the preparation process is cobalt chloride.

[0177] Example 5

[0178] The embodiment of the present application provides a composite insulating coating, which differs from the embodiment 1 in that the positively charged metal ions in the film layer are Mo ions. Accordingly, the metal salt used in the preparation process is molybdenum chloride.

[0179] Example 6

[0180] The embodiment of the present application provides a composite insulating coating, which differs from the embodiment 1 in that the positively charged metal ions in the film layer are Zn ions. Accordingly, the metal salt used in the preparation process is zinc chloride.

[0181] Example 7

[0182] The embodiment of the present application provides a composite insulating coating, which differs from the embodiment 1 in that the positively charged metal ions in the film layer are Mn ions. Accordingly, the metal salt used in the preparation process is manganese chloride.

[0183] Example 8

[0184] The embodiment of the present application provides a composite insulating coating, which is different from the embodiment 1 in that the positively charged metal ions in the film layer are V ions. Accordingly, the metal salt used in the preparation process is vanadium chloride.

[0185] Example 9

[0186] The embodiment of the present application provides a composite insulating coating, which differs from the embodiment 1 in that the positively charged metal ions in the film layer are Ce ions. Accordingly, the metal salt used in the preparation process is cerium chloride.

[0187] Example 10

[0188] The embodiment of the present application provides a composite insulating coating, which differs from Embodiment 1 in that the content of positively charged metal ions is 10%.

[0189] Embodiment 11

[0190] The embodiment of the present application provides a composite insulating coating, which differs from the embodiment 1 in that the content of positively charged metal ions is 12%.

[0191] Example 12

[0192] The embodiment of the present application provides a composite insulating coating, which differs from Embodiment 1 in that the content of positively charged metal ions is 20%.

[0193] Embodiment 13

[0194] The embodiment of the present application provides a composite insulating coating, which differs from Embodiment 1 in that the organic component in the film layer is polyamide ester PAE.

[0195] Comparative Example 1

[0196] This comparative example provides a composite insulating coating, which is different from Example 1 in that the film layer only includes polyvinyl alcohol (PVA).

[0197] Its preparation comprises the following steps:

[0198] ① Dissolve polyvinyl alcohol in an appropriate amount of aqueous solution to obtain solution A;

[0199] ② Spray solution A on the surface of the Al metal substrate, and form a film layer on the surface of the metal substrate after drying;

[0200] ③ Dissolve polyimide in an appropriate amount of N-methylpyrrolidone (NMP) solvent and spray it on the surface of the film layer formed on the surface of the metal substrate. After drying, an adhesive layer is formed on the surface of the film layer, thereby obtaining a composite insulating coating on the surface of the metal substrate. The upper layer of the composite insulating coating is a polyimide coating, and the lower layer is a polyvinyl alcohol coating.

[0201] Comparative Example 2

[0202] This comparative example provides a composite insulating coating, which differs from Example 1 in that the organic component in the film layer is polyethylene PE, which does not contain negatively charged functional groups, cannot form a Cr-O-Cr-O-Cr network structure with positively charged metal Cr ions in the film layer, and does not form chemical bonds with the polyimide in the bonding layer at the interface.

[0203] Comparative Example 3

[0204] This comparative example provides a composite insulating coating, which differs from Example 1 in that the organic matter in the bonding layer is polypropylene PP, which cannot form a chemical bond with the polyvinyl alcohol in the film layer at the interface.

[0205] The following performance tests were performed on the composite insulating coatings provided in the above embodiments and comparative examples:

[0206] 1. The thickness of the film layer and the thickness of the bonding layer in the composite insulating coating provided in each embodiment and comparative example, as well as the surface density, dielectric strength, softening temperature, corrosion resistance and other parameters of the composite insulating coating were measured respectively, and the test methods / conditions are as follows:

[0207] ①Thickness test method / conditions: Use a photothermal infrared thickness gauge to detect the signal of infrared thermal radiation (phase shift) to test the thickness of the coating;

[0208] ② Surface density test method / conditions: Use the weighing method to weigh the sample before and after coating, and calculate the coating surface density based on the surface area of ​​the coated sample;

[0209] ③ Dielectric strength test method / conditions: Using a withstand voltage tester, the applied voltage is increased through a series of processes until dielectric breakdown occurs to measure the dielectric strength of the sample;

[0210] ④ Softening temperature test method / conditions: Use a polymer Vicat softening point tester to apply a constant pressure to the sample and gradually heat the sample at a certain rate. The temperature measured when the sample deforms, flows or breaks is its softening point temperature;

[0211] ⑤ Anti-corrosion performance test method / conditions: Prepare Al foil coated with composite coating and use it as working electrode, use lithium metal as reference electrode and counter electrode, use buckle or electrolytic cell device, and use cyclic voltammetry to test the corrosion potential of the working electrode in electrolyte, the unit is V (vs Li / Li + ).

[0212] The test results are shown in Table 1 below:

[0213] Table 1

[0214]

[0215] It can be seen from the test data in Table 1 above that the composite insulating coating provided in the embodiment of the present application has a surface density of 6-7 mg / m2 when the film layer thickness is 20 μm, the bonding layer thickness is 20 μm, and the total thickness is 40 μm. 2 , wherein the surface density of the composite insulating coating of Example 13 is 6.85 mg / m 2 ; The dielectric strength is not less than 24.9KV / mm, among which the dielectric strength of the composite insulating coating of Example 6 is as high as 27.9KV / mm; the softening temperature is 180-200°C; the corrosion potential is not less than 3.72V (vs Li / Li + ), wherein the corrosion potential of the composite insulating coating of the embodiment is as high as 3.97V (vs Li / Li +). However, the composite insulating coating provided in Example 1 cannot form a dynamically cross-linked network structure because no positively charged metal complex ions are added to the film layer, which affects the electrolyte corrosion blocking performance and reduces the corrosion potential. The composite insulating coating provided in Example 2 cannot complex metal elements to achieve corrosion blocking because the organic component in the film layer uses PE and has no oxygen-containing functional groups, and the corrosion potential is also low. The composite insulating coating provided in Example 3 cannot form an interface bond with the film layer because the organic matter in the bonding layer uses PP, and the composite interface is unstable, resulting in a significant decrease in softening temperature, low corrosion resistance, and reduced corrosion potential.

[0216] 2. The bonding layer in the composite insulating coating prepared in Example 1 was tested by Raman spectroscopy and infrared spectroscopy, wherein the Raman spectroscopy test is shown in the attached figure. Figure 7 Shown: 1430-1470cm -1 Corresponding to the characteristic peak of D band of carbon atom in organic matter; 2840-2890cm -1 Corresponding to the characteristic peak of 2D band of carbon atom in organic matter. The infrared spectrum test chart is as attached Figure 8 Shown: 1734cm -1 Corresponding to O=CO vibration peak; 1556cm -1 Corresponding to C=C vibration peak; 1437cm -1 Corresponding to CH3 / CH2 deformation vibration peak; 1106cm -1 The corresponding -OH absorption peak proves that the bonding layer constructed in the composite insulating coating prepared in Example 1 has oxygen-containing functional groups.

[0217] 3. The film layer of the composite insulating coating prepared in Example 1 was subjected to an X-ray photoelectron spectroscopy (XPS) test. The test results are shown in the attached figure. Fig. 9 The full spectrum of XPS, as well as Fig.10 As shown in the Cr2p spectrum of XPS, it can be seen from the X-ray photoelectron energy spectrum that the film layer constructed in the composite insulating coating prepared in Example 1 contains Cr element, and Cr and oxygen-containing functional groups form a stable Cr-O-Cr-O-Cr network structure.

[0218] 4. Electrochemical corrosion test was performed on the composite insulating coating prepared in Example 1. The Al explosion-proof valve sample coated with the composite insulating coating of Example 1 was immersed in an electrolyte for electrochemical corrosion test verification. The test results are shown in the attached figure. Fig.11 As shown: the explosion-proof valve coated with the composite insulating coating of the embodiment of the present application has a higher corrosion potential and a lower corrosion current than the explosion-proof valve without a coating, wherein the current increase in the 3.5V-4.25V interval is mainly contributed by the electrochemical corrosion current of Al aluminum; the current increase in the 4.25V-4.90V interval is mainly contributed by the decomposition current of the electrolyte, proving that the composite insulating coating prepared in Example 1 effectively inhibits the electrochemical corrosion of Al of the explosion-proof valve in the electrolyte.

[0219] 5. X-ray photoelectron spectroscopy (XPS) tests were performed on the samples after the electrochemical corrosion test. The test results are shown in the attached Fig.12 As shown: Al-O / Al-F signals appear on the explosion-proof valve without coating after electrochemical corrosion, indicating that a large amount of aluminum oxide / aluminum fluoride corrosion products are generated on the surface of the explosion-proof valve after corrosion. However, the explosion-proof valve with the composite insulating coating of Example 1 of the present application has CC and C=O peaks in the C1s spectrum after electrochemical corrosion, and Cr2p3 and Cr2p1 peaks in the Cr2p spectrum, proving that the composite insulating coating of the present application is still stably bonded to the surface of the explosion-proof valve after the electrochemical corrosion test. There is basically no Al-O / Al-F signal in the Al2p spectrum, proving that the coating can effectively block corrosion.

[0220] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The scope of protection of the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims. Therefore, the scope of protection of the present application shall be based on the scope of protection of the claims.

Claims

1. A composite insulating coating, characterized in that: It comprises a laminated film layer and an adhesive layer, wherein the film layer is adhered to the surface of an application substrate, the film layer comprises an organic component with negatively charged functional groups and positively charged metal ions, and the positively charged metal ions form a dynamically cross-linked network structure with the negatively charged functional groups; the adhesive layer is arranged on the surface of the film layer, has electrolyte barrier properties, the adhesive layer comprises an organic substance containing polar functional groups, and the polar functional groups in the adhesive layer form chemical bonds with the negatively charged functional groups in the film layer at the interface.

2. The composite insulating coating according to claim 1, characterized in that: In the film layer, the mass percentage of the positively charged metal ions is 1% to 30%, preferably 10% to 20%.

3. The composite insulating coating according to claim 2, characterized in that: In the film layer, the positively charged metal ions include at least one of Cr ions, Zr ions, Ni ions, Co ions, Mo ions, Zn ions, Mn ions, V ions, and Ce ions.

4. The composite insulating coating according to any one of claims 1 to 3, characterized in that: The organic component with negatively charged functional groups includes at least one of polyester, polyether, polyol, polyolefin acid, polyaldehyde, polyketone, polyamide and polysiloxane.

5. The composite insulating coating according to claim 4, characterized in that: The negatively charged functional groups in the organic component include oxygen-containing functional groups A.

6. The composite insulating coating according to claim 5, characterized in that: The oxygen-containing functional group A includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an ester group, an aldehyde group, a ketone group, an ether group, and an amide group.

7. The composite insulating coating according to claim 5 or 6, characterized in that: The expression of the dynamically cross-linked network structure includes -M1-O-M2-O-…-Mi-, wherein M1, M2, Mi are independently selected from at least one of Cr, Zr, Ni, Co, Mo, Zn, Mn, V, and Ce, and i is a positive integer greater than 2.

8. The composite insulating coating according to any one of claims 1 to 3, 5 or 6, characterized in that: The polar functional group in the organic matter includes at least one of a nitrogen-containing functional group, an oxygen-containing functional group B, and a fluorine-containing functional group.

9. The composite insulating coating according to claim 8, characterized in that: The nitrogen-containing functional group includes at least one of an amide group, an amine group, and an imine group; And / or, the oxygen-containing functional group B includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group, an ester group, an aldehyde group, a ketone group, an ether group, and an amide group; And / or, the fluorine-containing functional group includes at least one of a fluorocarbon group and a fluorooxy group.

10. The composite insulating coating according to claim 8, characterized in that: The polar functional groups in the organic matter and the negatively charged functional groups in the organic component form hydrogen bonds at the interface between the film layer and the adhesive layer.

11. The composite insulating coating according to claim 8, characterized in that: The organic matter includes at least one of modified polyolefin, polyvinylidene fluoride, polyamide, polyimide, polyacrylonitrile, modified polyaramid, polyetheretherketone, polyethylene terephthalate, polyphenylene sulfide and polybenzimidazole.

12. The composite insulating coating according to claim 11, characterized in that: The molar molecular weight of the organic matter is 3000 g / mol to 300000 g / mol.

13. The composite insulating coating according to any one of claims 1 to 3, 5 to 6, 10 to 12, characterized in that: The thickness of the composite insulating coating is 10 μm to 1000 μm, preferably 40 μm to 500 μm; And / or, the thickness of the film layer is 5 μm to 500 μm, preferably 20 μm to 250 μm; And / or, the thickness of the adhesive layer is 5 μm to 500 μm, preferably 20 μm to 250 μm.

14. The composite insulating coating according to any one of claims 1 to 3, 5 to 6, 10 to 12, characterized in that: The surface density of the composite insulating coating is 0.5 mg / m 2 ~50 mg / m 2 , preferably 1 mg / m 2 ~20 mg / m 2 .

15. The composite insulating coating according to any one of claims 1 to 3, 5 to 6, 10 to 12, characterized in that: The dielectric strength of the composite insulating coating is not less than 5000 V / mm, preferably not less than 10000 V / mm.

16. The composite insulating coating according to any one of claims 1 to 3, 5 to 6, 10 to 12, characterized in that: The softening temperature of the composite insulating coating is 70°C to 250°C, preferably 90°C to 200°C.

17. A method for preparing a composite insulating coating, characterized in that: The following steps are involved: After preparing a mixed slurry including an organic component with a negatively charged functional group and a metal component with a positively charged metal ion, the mixed slurry is made into a film layer on the surface of an application substrate to form a skin film layer; In the film layer, the positively charged metal ions and the negatively charged functional groups form a dynamic cross-linked network structure; Organic matter containing polar functional groups is made into a film layer on the surface of the film layer to form an adhesive layer with electrolyte barrier properties, thereby obtaining a composite insulating coating; at the interface between the film layer and the adhesive layer, the polar functional groups in the adhesive layer form chemical bonds with the negatively charged functional groups in the film layer.

18. The method for preparing the composite insulating coating according to claim 17, characterized in that: The preparation of the film layer comprises the following steps: Dissolving an organic component having a negatively charged functional group in a first solvent to obtain a first solution; dissolving a metal component having positively charged metal ions in a second solvent to obtain a second solution; The first solution and the second solution are mixed, washed, and extracted to obtain a polymer complexed with metal ions; After the metal ion complexing polymer is dissolved in an organic solvent, a film layer is formed on the surface of the application substrate to obtain a film layer.

19. The method for preparing the composite insulating coating according to claim 18, characterized in that: The metal component includes an organic metal salt and / or an inorganic metal salt; The organic component comprises at least one of polyester, polyether, polyol, polyolefin acid, polyaldehyde, polyketone, polyamide and polysiloxane; The first solvent and / or the second solvent are independently selected from at least one of a polar solvent, a dipolar solvent, and a non-polar solvent.

20. The method for preparing a composite insulating coating according to any one of claims 17 to 19, characterized in that: The preparation of the bonding layer comprises the following steps: preparing the organic matter containing polar functional groups into a film layer with a preset morphology, and then compounding it onto the surface of the film layer by hot pressing to obtain the bonding layer; Alternatively, after the organic matter containing polar functional groups is made into an insulating paste, the insulating paste is deposited on the surface of the film layer and dried to obtain the bonding layer.

21. A battery cell, characterized in that: The battery cell includes a battery pole core, a battery cell shell and a cover assembly, the cover assembly includes an explosion-proof valve, and at least the inner wall surface of the battery cell shell and / or the inner side surface of the explosion-proof valve is provided with a composite insulating coating as described in any one of claims 1 to 16, or a composite insulating coating prepared by the method as described in any one of claims 17 to 20.

22. A battery module, characterized in that: The battery module comprises a plurality of battery cells as claimed in claim 21.

23. A battery pack, characterized in that: The battery pack includes a plurality of battery modules as described in claim 22.

24. An electrical equipment, characterized in that: The electrical equipment includes the battery cell as described in claim 21, or the battery module as described in claim 22, or the battery pack as described in claim 23.